Positive electrode active material and secondary battery

A nickel-manganese-cobalt-based positive electrode active material with tailored surface and interior compositions addresses lithium-ion secondary battery challenges, enhancing discharge capacity and safety through stabilized crystal structures and improved lithium ion diffusion.

CN119156719APending Publication Date: 2024-12-17SEMICON ENERGY LAB CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380034772.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-21
Filing Date
2023-04-07
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Lithium-ion secondary batteries face challenges in charge and discharge rate characteristics, discharge capacity, cycle characteristics, reliability, safety, and cost, necessitating improvements in positive electrode active materials.

Method used

A positive electrode active material comprising nickel, manganese, and cobalt with specific surface and interior compositions of added elements like magnesium, aluminum, and titanium, which stabilizes the crystal structure and enhances lithium ion diffusion paths, thereby improving charge and discharge rates and safety.

Benefits of technology

The material achieves high discharge capacity and safety by maintaining a stable crystal structure, suppressing short-circuit currents, and ensuring reliable performance even at high charging voltages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119156719A_ABST
    Figure CN119156719A_ABST
Patent Text Reader

Abstract

Provided are: a positive electrode active material having excellent charge / discharge rate characteristics; and a secondary battery using the positive electrode active material. Provided is a positive electrode active material in which the crystal grain size calculated from an XRD pattern is 150 nm or more, and the ratio of nickel in the interior to the total number of atoms of a transition metal is higher than the ratio in a first surface layer part and a second surface layer part. The ratio of the number of atoms of at least one element selected from cobalt and manganese in the second surface layer portion to the total number of atoms of the transition metal is higher than the ratio in the interior, and the concentration of at least one of the added elements in the first surface layer portion is higher than the concentration in the interior and the second surface layer portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to an article, method or manufacturing method. In addition, the present invention relates to a process, machine, product or composition of matter. One embodiment of the present invention relates to a storage device including a secondary battery, a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device or a manufacturing method thereof.

[0002] Note that in this specification, electronic equipment refers to any device having a power storage device. An electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all electronic equipment. Background Art

[0003] In recent years, the research and development of various power storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries and all-solid batteries has become increasingly popular. In particular, with the development of the semiconductor industry, the demand for high-output, high-capacity lithium-ion secondary batteries has increased dramatically. As a rechargeable energy supply source, it has become a necessity in the modern information society.

[0004] In particular, secondary batteries for portable electronic devices are required to have a larger discharge capacity per unit weight and higher cycle characteristics. In order to meet these requirements, improvements in positive electrode active materials contained in the positive electrode of secondary batteries are being actively carried out (for example, Patent Document 1 and Non-Patent Document 1). [Prior technical literature] [Patent Document]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 2020-068210

[0006] [Non-patent document 1] S.-W.Woo et al., “Improvement of electrochemical and thermal properties of Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2 positive electrode materials by multiple metal(Al,Mg)substitution”, Electrochimica Acta 54(2009)3851-3856 Summary of the invention Technical problem to be solved by the invention

[0007] Lithium-ion secondary batteries still have room for improvement in various aspects such as charge and discharge rate characteristics, discharge capacity, cycle characteristics, reliability, safety, and cost.

[0008] Therefore, the positive electrode active material used for the above-mentioned lithium ion secondary battery is also required to improve the charge and discharge rate characteristics, discharge capacity, cycle characteristics, reliability, safety, cost and other issues when used in the secondary battery.

[0009] One of the purposes of one embodiment of the present invention is to provide a positive electrode active material or a composite oxide that can be used in a lithium ion secondary battery and has excellent charge and discharge rate characteristics. In addition, one of the purposes of one embodiment of the present invention is to provide a secondary battery with high safety or reliability.

[0010] Another object of one embodiment of the present invention is to provide a positive electrode active material, a composite oxide, a power storage device, or a method for producing the same.

[0011] Note that the description of these purposes does not prevent the existence of other purposes. One embodiment of the present invention does not need to achieve all of the above purposes. In addition, purposes other than the above purposes can be extracted from the description of the specification, drawings, and claims. Solutions to technical problems

[0012] One embodiment of the present invention is a positive electrode active material, which includes a transition metal M, oxygen and an added element, the transition metal M is nickel, manganese and cobalt, the added element is one or more selected from magnesium, aluminum, calcium, titanium and zirconium, the positive electrode active material includes a first surface portion, a second surface portion and an interior, the second surface portion is closer to the interior than the first surface portion, the proportion of nickel in the interior to the total number of atoms of the transition metal M is higher than the proportion in the first surface portion and the second surface portion, the proportion of the number of atoms of at least one element selected from cobalt and manganese in the second surface portion to the total number of atoms of the transition metal M is higher than the proportion in the interior, and the concentration of at least one element of the added elements in the first surface portion is higher than the concentration in the interior and the second surface portion.

[0013] In addition, another embodiment of the present invention is a secondary battery, which includes a positive electrode and a negative electrode containing a positive electrode active material, the positive electrode active material includes a transition metal M, oxygen and an added element, the transition metal M is nickel, manganese and cobalt, the added element is one or more selected from magnesium, aluminum, calcium, titanium and zirconium, the positive electrode active material includes a first surface portion, a second surface portion and an interior, the second surface portion is closer to the interior than the first surface portion, the proportion of nickel in the interior to the total number of atoms of the transition metal M is higher than the proportion in the first surface portion and the second surface portion, the proportion of the number of atoms of at least one element selected from cobalt and manganese in the second surface portion to the total number of atoms of the transition metal M is higher than the proportion in the interior, and the concentration of at least one element of the added elements in the first surface portion is higher than the concentration in the interior and the second surface portion.

[0014] In the above embodiment, the crystallite size of the positive electrode active material calculated from the XRD pattern is preferably 150 nm or more.

[0015] In addition, another embodiment of the present invention is a positive electrode active material, which includes a transition metal M and oxygen, the transition metal M is nickel, manganese and cobalt, the grain size of the positive electrode active material calculated from the XRD pattern is greater than 150nm, and a secondary battery using the positive electrode active material is charged by CC / CV (4.5V, 100mA / g, 10mA / g cut) at 25°C and then CC (constant current) is performed at 2000mA / g. The discharge capacity obtained is greater than 70mAh / g.

[0016] In addition, another embodiment of the present invention is a secondary battery, which includes a positive electrode and a negative electrode containing a positive electrode active material, the positive electrode active material includes a transition metal M and oxygen, the transition metal M is nickel, manganese and cobalt, the grain size of the positive electrode active material calculated from the XRD pattern is greater than 150nm, and the secondary battery is charged by CC / CV (4.5V, 100mA / g, 10mA / gcut) at 25°C and then CC (constant current) is charged at 2000mA / g. The discharge capacity is greater than 70mAh / g. Effects of the Invention

[0017] According to one embodiment of the present invention, a positive electrode active material or a composite oxide can be provided, which can be used in a lithium ion secondary battery and has excellent charge and discharge rate characteristics. In addition, according to one embodiment of the present invention, a secondary battery with high safety or reliability can be provided.

[0018] Furthermore, according to one embodiment of the present invention, a positive electrode active material, a composite oxide, a power storage device, or a method for producing the same can be provided.

[0019] Note that the description of these effects does not prevent the existence of other effects. One mode of the present invention does not need to have all of the above effects. In addition, the description of the specification, drawings, and claims clearly indicates that there are effects other than the above effects, and effects other than the above effects can be obtained from the description of the specification, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figures 1A to 1C It is a cross-sectional view of the positive electrode active material. Figure 2 This is an example of a TEM image in which the crystal orientation is roughly uniform. Figure 3A This is an example of a STEM image with roughly uniform crystal orientation. Figure 3B This is the FFT pattern of the rock salt type crystal RS region. Figure 3C It is the FFT pattern of the region of layered rock salt type crystal LRS. Figure 4A and Figure 4B It is a cross-sectional view of the positive electrode active material. FIG. 5A to FIG. 5C It is a cross-sectional view of the positive electrode active material. Figure 6 It is a diagram for explaining a method for producing a positive electrode active material. Figure 7 It is a diagram for explaining a method for producing a positive electrode active material. Figure 8 It is a diagram for explaining a method for producing a positive electrode active material. Fig. 9 It is a diagram for explaining a method for producing a positive electrode active material. FIG. 10A to FIG. 10D It is a cross-sectional view illustrating an example of a positive electrode of a secondary battery. Fig.11A This is an exploded perspective view of a coin-type secondary battery. Fig. 11B is a perspective view of a coin-type secondary battery. Fig. 11C It is a cross-sectional stereogram. Fig. 12A An example of a cylindrical secondary battery is shown. Fig. 12B An example of a cylindrical secondary battery is shown. Fig. 12C A plurality of examples of cylindrical secondary batteries are shown, Fig.12D An example of a power storage system including a plurality of cylindrical secondary batteries is shown. Fig.13A and Fig. 13B is a diagram illustrating an example of a secondary battery, Fig. 13C It is a diagram showing the internal state of a secondary battery. FIG. 14A to FIG. 14C It is a diagram for explaining an example of a secondary battery. Fig.15A and Fig. 15B It is a diagram showing the appearance of a secondary battery. FIG. 16A to FIG. 16C It is a diagram for explaining a method for manufacturing a secondary battery. Fig.17A is a perspective view showing a battery pack according to one embodiment of the present invention. Fig. 17B is the block diagram of the battery pack, Fig. 17C is a block diagram of a vehicle including a battery pack. 18A to 18D is a diagram illustrating an example of a transport vehicle. Fig.18E This is a diagram illustrating an example of an artificial satellite. Fig.19A is a diagram showing an electric bicycle, Fig.19B is a diagram showing a secondary battery of an electric bicycle, Fig.19C It is a figure explaining a small motorcycle. FIG. 20A to FIG. 20D It is a diagram for explaining an example of an electronic device. FIG. 21A to FIG. 21F This is a surface SEM image of the positive electrode active material. Fig.22A and Fig. 22B This is a graph showing the discharge rate characteristics of the secondary battery. Fig.23A and Fig. 23B is a graph showing the charge rate characteristics of a secondary battery. FIG. 24A to FIG. 24H This is a surface SEM image of the positive electrode active material. FIG. 25A to FIG. 25C This is a cross-sectional SEM image of the positive electrode active material. FIG. 25D to FIG. 25F is a graph showing the results of EDX point analysis. Modes for Carrying Out the Invention

[0021] Hereinafter, examples of embodiments of the present invention will be described with reference to the drawings, etc. Note that the present invention should not be construed as being limited to the following examples of embodiments. The embodiments of the present invention may be modified within the scope of the present invention.

[0022] In addition, in this specification, etc., the particles are not limited to spherical (circular cross-sectional shape), and the cross-sectional shape of each particle can also be elliptical, rectangular, trapezoidal, conical, a quadrilateral with curved corners, an asymmetric shape, etc., and each particle can also be amorphous.

[0023] In addition, "homogeneous" refers to a state in which a certain element (for example, A) in a solid containing multiple elements (for example, A, B, C) has the same characteristics and is distributed in a specific area. The element concentration between specific areas is substantially the same. For example, the difference in the detection amount of a certain element in a specific area (for example, the count of STEM-EDX) is within 10%. As specific areas, for example, a surface part, a surface, a convex part, a concave part, an interior, etc. can be cited.

[0024] In addition, the positive electrode active material to which the additional element is added is sometimes recorded as a composite oxide, a positive electrode material, a positive electrode material for a secondary battery, etc. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a compound. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composition. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composite.

[0025] In addition, when describing the characteristics of each particle of the positive electrode active material in this specification, it is not necessarily necessary for all particles to have the characteristics. For example, as long as 50% or more, preferably 70% or more, and more preferably 90% or more of three or more positive electrode active material particles selected irregularly have the characteristics, it can be said that the characteristics of the positive electrode active material and the secondary battery including the positive electrode active material are sufficiently improved.

[0026] Generally speaking, as the charging voltage of the secondary battery increases, the voltage of the positive electrode also increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at a high charging voltage. The crystal structure of the positive electrode active material in the charged state is stable, so the reduction of the charge and discharge capacity due to repeated charge and discharge can be suppressed.

[0027] In addition, the short circuit of the secondary battery can cause heat and fire in addition to causing defects in the charging operation and / or discharging operation of the secondary battery. In order to achieve a safe secondary battery, it is preferred to suppress the short-circuit current also at a high charging voltage. The positive electrode active material of one embodiment of the present invention can also suppress the short-circuit current at a high charging voltage. Therefore, a secondary battery that achieves both high discharge capacity and safety can be manufactured.

[0028] Note that, unless otherwise specified, the materials (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) included in the secondary battery in the state before degradation are described. In addition, the following situation is not called degradation: the situation where the discharge capacity is reduced due to the aging treatment (also referred to as the burn-in treatment) in the stage of manufacturing the secondary battery. For example, the following situation can be referred to as the state before degradation: the situation with a discharge capacity of more than 97% of the rated capacity of a lithium-ion secondary single cell and a lithium secondary battery pack (hereinafter also referred to as a lithium-ion secondary battery). When using lithium-ion secondary batteries for portable devices, the rated capacity is based on JIS C 8711:2019. When using lithium-ion secondary batteries other than the above, it is not limited to the above-mentioned JIS specifications, but is based on various JIS, IEC specifications, etc. for electric vehicle propulsion and industrial use.

[0029] In addition, the state before deterioration of the materials included in the secondary battery is sometimes referred to as an initial item or initial state, and the state after deterioration (a state where the discharge capacity is less than 97% of the rated capacity of the secondary battery) is referred to as an item in use or in a state in use or a used item or used state.

[0030] (Implementation Method 1) In this embodiment, a positive electrode active material 100 according to one embodiment of the present invention will be described with reference to FIGS. 1 to 5 .

[0031] <Contains elements> The positive electrode active material 100 includes lithium, a transition metal M, and oxygen. The transition metal M is one or more selected from nickel, manganese, and cobalt. The positive electrode active material 100 preferably includes an additive element in addition to the transition metal M. Alternatively, the positive electrode active material 100 may include a material in which an additive element is added to nickel-manganese-lithium cobalt oxide.

[0032] In order for the positive electrode active material of a lithium ion secondary battery to maintain charge neutrality even when lithium ions are inserted or released, it is necessary to contain a transition metal that can be oxidized and reduced. The positive electrode active material 100 of one embodiment of the present invention contains nickel, manganese, and cobalt as a transition metal M that participates in the oxidation-reduction reaction.

[0033] When the proportion of nickel in the transition metal M contained in the positive electrode active material 100 is large, it is preferred because the charge and discharge capacity can be easily increased even at a low charging voltage compared to the case where cobalt accounts for the majority. Therefore, for example, nickel in the transition metal M preferably accounts for 50% or more, more preferably 60% or more, and further preferably 75% or more.

[0034] As the additive element contained in the positive electrode active material 100, one or more selected from magnesium, aluminum, calcium, titanium, zirconium, fluorine, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine and beryllium are preferably used. In addition, the ratio of the number of atoms of the additive element to the total number of atoms of the transition metal M is preferably less than 25 atomic%, more preferably less than 10 atomic%, and further preferably less than 5 atomic%.

[0035] As described below, these additional elements can further stabilize the crystal structure of the positive electrode active material 100. In addition, the additional elements in this specification and the like are synonymous with a part of a mixture or a raw material.

[0036] Note that magnesium, aluminum, calcium, titanium, zirconium, fluorine, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, and beryllium do not necessarily need to be contained as additive elements.

[0037] <Single Particle> The particles of the positive electrode active material 100 are preferably single crystals. When the positive electrode active material 100 is a single crystal particle, the single crystal particle is sometimes also referred to as a single particle. Alternatively, the grain size of the positive electrode active material 100 is preferably large.

[0038] When the primary particles are large, the formation of secondary particles due to the aggregation and sintering of the primary particles can be suppressed. In addition, when the primary particle size is large, the grain size calculated by the half width of the diffraction pattern of XRD is also large. Therefore, when the positive active material 100 is a single particle or the grain size calculated by the diffraction pattern of XRD is large, compared with the positive active material formed by sintering a plurality of primary particles, no or few cracks are generated between the primary particles. It can be expected that even if the volume of the positive active material 100 changes due to charge and discharge, cracks can be suppressed.

[0039] For example, the crystallite size calculated from the half width of the diffraction pattern of XRD is preferably 150 nm or more, more preferably 180 nm or more, and further preferably 200 nm or more.

[0040] However, when it is desired to make the single crystal larger or the grain size larger, it is sometimes necessary to heat for a long time or at a high temperature or to heat after adding lithium that is too much than the stoichiometric composition. However, the long heating process reduces productivity. In addition, heating at high temperatures may cause cation mixing of nickel ions and lithium ions. In addition, too much lithium may also cause gelation of the binder when manufacturing the slurry of the positive electrode. In order to avoid the above-mentioned shortcomings, it is preferred that the size of the single crystal and the size of the crystallite are moderate.

[0041] For example, the crystal size calculated from the XRD diffraction pattern is preferably less than 1000 nm, more preferably less than 800 nm. The positive electrode active material having a crystal size calculated from the XRD diffraction pattern within the above range has a sufficiently large crystal size and can be said to be a positive electrode active material having characteristics close to a single particle.

[0042] Note that the XRD pattern used when calculating the half width can be obtained in the state of only the positive electrode active material, or in the state of the positive electrode including a current collector, a binder, and a conductive material in addition to the positive electrode active material. Note that in the positive electrode state, the positive electrode active material may be oriented due to the influence of pressure in the manufacturing process, etc. It may be difficult to accurately calculate the grain size when the orientation of the positive electrode active material is strong. Therefore, it is more preferable to use a method of reducing the orientation, such as removing the positive electrode active material layer from the positive electrode and using a solvent to appropriately remove the binder in the positive electrode active material layer, and then placing it in a sample holder to obtain the XRD diffraction pattern.

[0043] < <xrd>> The XRD measurement apparatus and conditions used to calculate the crystal grain size are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: CuKα1 ray Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 90° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm

[0044] When the sample to be measured is a powder sample, the sample can be installed by placing it in a glass sample holder; or sprinkling the sample on a silicon non-reflective plate coated with grease; etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be installed according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0045] The crystallite size can be calculated by analyzing the obtained XRD diffraction pattern using crystal structure analysis software (for example, TOPAS ver. 3).

[0046] <Surface layer> Figure 1A This is a cross-sectional view of a single particle of the positive electrode active material 100. The positive electrode active material 100 preferably includes a surface portion and an inner portion 100c. The surface portion preferably includes a surface portion 100a and a surface portion 100b. The surface portion 100b is closer to the inner portion 100c than the surface portion 100a.

[0047] In this specification, etc., the surface layer 100a of the positive electrode active material 100 refers to, for example, a region within 200 nm from the surface to the inside. In addition, the surface layer 100b of the positive electrode active material 100 refers to, for example, a region outside 200 nm and within 1000 nm from the surface to the inside. The surface generated by cracks and / or fissures can also be referred to as a surface. The surface layer is synonymous with the vicinity of the surface, the region near the surface, or the shell.

[0048] In addition, a region deeper than the surface layer portion in the positive electrode active material is referred to as an inner portion 100 c . The inner portion 100 c is synonymous with an inner region or a core.

[0049] In addition, the surface of the positive electrode active material 100 refers to the surface of the composite oxide including the above-mentioned surface layer and the internal 100c. Therefore, the positive electrode active material 100 does not include carbonates, hydroxyls, etc. chemically adsorbed after manufacturing. In addition, electrolytes, adhesives, conductive agents, or compounds derived from them attached to the positive electrode active material 100 are not included. In addition, the surface of the positive electrode active material 100 in the cross-sectional STEM (scanning transmission electron microscope) image, etc. refers to the boundary between the area where the coupling image of the electron beam is observed and the area where the coupling image is not observed, and refers to the outermost side of the area where the bright spot of the nucleus of the metal element with an atomic number greater than lithium is confirmed. The surface in the cross-sectional STEM image, etc. can also be judged based on an analysis with higher spatial resolution, such as the analysis results of the electron energy loss spectrum (EELS).

[0050] Figure 1B and Figure 1C 1 is a cross-sectional view of a positive electrode active material 100, which is a secondary particle and includes primary particles with a large grain size and a grain boundary 101. The surface layer portion 100a and the surface layer portion 100b may be as follows Figure 1B As shown, it does not exist around the grain boundary 101, and it can also be Figure 1C Shown exists.

[0051] In addition, the grain boundary 101 refers to, for example: a portion where the primary particles included in the positive electrode active material 100 are bonded together; a portion where the crystal orientation changes inside the positive electrode active material 100, that is, a portion where the bright lines and dark lines in the scanning transmission electron microscope (STEM) image are repeatedly discontinuous, a portion containing multiple crystal defects, a portion with a disordered crystal structure, etc. In addition, a crystal defect refers to a defect observable by a cross-sectional TEM (transmission electron microscope), a cross-sectional STEM image, etc., that is, a structure where other elements enter the lattice, a void, etc. The grain boundary 101 can be said to be a type of surface defect. In addition, the vicinity of the grain boundary 101 refers to the area within 10 nm from the grain boundary 101.

[0052] Grain boundaries are a type of surface defect. Therefore, like the surface, they tend to be unstable and are prone to changes in the crystal structure. Therefore, the higher the concentration of added elements at the grain boundaries and their vicinity, the more effectively the changes in the crystal structure can be suppressed, as described later.

[0053] In addition, when the concentration of the added element at the grain boundary 101 and its vicinity is high, even when cracks are generated along the grain boundary of the positive electrode active material 100 of one embodiment of the present invention, the concentration of the added element near the surface where the cracks are generated becomes high. Therefore, the crystal structure can also be further stabilized in the surface layer where the cracks are generated.

[0054] <Crystal Structure> The positive electrode active material 100 of one embodiment of the present invention is in a discharge state, that is, in a Li x When x=1 in MO2 (M is at least one of Ni, Co, and Mn), it is preferred to have a layered rock salt type crystal structure belonging to the space group R-3m. The layered rock salt type composite oxide has a high discharge capacity and a two-dimensional lithium ion diffusion path, which is suitable for the insertion and extraction reaction of lithium ions, and is excellent as a positive electrode active material for secondary batteries. Therefore, in particular, the inner part 100c that occupies most of the volume of the positive electrode active material 100 preferably has a layered rock salt type crystal structure.

[0055] On the other hand, the surface portion of the positive electrode active material 100 of one embodiment of the present invention preferably strengthens the layered structure composed of the octahedron of the transition metal M and oxygen in the inner 100c to prevent the layered structure from collapsing even if lithium is separated from the positive electrode active material 100 due to charging. Alternatively, the surface portion is preferably used as a barrier film for the positive electrode active material 100. Alternatively, the surface portion of the outer peripheral portion of the positive electrode active material 100 preferably strengthens the positive electrode active material 100. Here, strengthening refers to suppressing the structural changes of the surface portion and the inner 100c of the positive electrode active material 100 such as the separation of oxygen and / or suppressing the oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100. That is, "serving as a barrier film" means, for example, that the surface portion suppresses the structural changes of the positive electrode active material 100 and suppresses the oxidative decomposition of the electrolyte.

[0056] Therefore, the surface layer part preferably has a composition and a crystal structure different from those of the inner part 100 c. In addition, the composition and the crystal structure of the surface layer part at room temperature (25° C.) are preferably more stable than those of the inner part 100 c. For example, at least a portion of the surface portion of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface portion preferably has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface portion preferably has characteristics of both a layered rock salt type and a rock salt type crystal structure.

[0057] The surface part is the area where lithium ions are first separated during charging, and it is also the area where the lithium concentration is likely to be lower than that of the inner 100c. In addition, it can also be said that some of the bonds among the atoms on the surface of the positive electrode active material 100 contained in the surface part are cut. Therefore, it can also be said that the surface part is likely to become unstable and the crystal structure is likely to deteriorate. On the other hand, as long as the surface part can be sufficiently stabilized, the Li x When x in MO2 is small, the layered structure composed of transition metal M and oxygen octahedrons in the inner portion 100 c can be less likely to collapse. Furthermore, the deviation of the layer composed of transition metal M and oxygen octahedrons in the inner portion 100 c can be suppressed.

[0058] In order to make the surface layer part have a stable composition and crystal structure, the surface layer part preferably contains an additive element, and more preferably contains a plurality of additive elements. In addition, the composition of the transition metal M is preferably different between the surface layer part and the inner part 100c.

[0059] For example, the concentration peak of the additive element is preferably located in the surface layer portion, and more preferably located in the surface layer portion 100 a closer to the surface.

[0060] In addition, the concentration of at least one of cobalt and manganese in the transition metal M in the surface portion is preferably higher than that in the inner portion 100c. Similarly, the nickel concentration in the inner portion 100c is preferably higher than the nickel concentration in the surface portion. In addition, at least one of cobalt and manganese preferably has a concentration gradient that increases toward the surface of the positive electrode active material 100. Similarly, nickel preferably has a concentration gradient that increases toward the inside of the positive electrode active material 100.

[0061] Therefore, the surface layer portion 100 b is preferably a region where the concentrations of cobalt and manganese are higher than those in the inner portion 100 c although there is no concentration peak of the added element.

[0062] In addition, the concentration of one or more selected from the additive elements in the surface portion 100a is preferably higher than that in the surface portion 100b and the inner portion 100c. In addition, one or more selected from the additive elements contained in the positive electrode active material 100 preferably has a concentration gradient. In addition, More preferably, the distribution of the added element in the positive electrode active material 100 is different. For example, more preferably, the depth of the added element concentration peak from the surface is different. Here, the concentration peak refers to the maximum value of the concentration in the surface portion 100a or the range below 200nm from the surface.

[0063] For example, a part of the added elements such as magnesium, fluorine, nickel, titanium, silicon, phosphorus, boron, calcium, etc. preferably has a concentration gradient that becomes higher from the inner part 100 c toward the surface.

[0064] As described below, these additive elements can make the crystal structure of the positive electrode active material 100 more stable. Note that the additive elements can be contained not only in the additive element source, but also slightly contained in the transition metal M source, etc. Regardless of the source of the additive elements, as long as the concentration and distribution of the additive elements are appropriate, they can contribute to the chemical stability of the positive electrode active material 100.

[0065] For example, when magnesium, one of the additive elements, is present at an appropriate concentration at the lithium site of the surface layer, it is easy to maintain the layered rock salt type crystal structure of the inner 100c. This is because the magnesium present at the lithium site acts as a support between the MO2 layers.

[0066] If magnesium has an appropriate concentration, it has no negative impact on the insertion and removal of lithium accompanying charge and discharge, so the above advantages can be achieved. However, excess magnesium may have a negative impact on the insertion and removal of lithium. In addition, the effect of contributing to the stabilization of the crystal structure sometimes becomes smaller. In addition, there is the following concern: useless magnesium compounds (oxides and fluorides, etc.) that neither replace the lithium position nor the transition metal M position are segregated on the surface of the positive electrode active material and become the resistance component of the secondary battery. In addition, the increase in the magnesium concentration of the positive electrode active material sometimes reduces the discharge capacity of the positive electrode active material. This is because the excess magnesium enters the lithium position and the amount of lithium contributing to charge and discharge is reduced.

[0067] In addition, aluminum may exist in the transition metal M position in the layered rock salt type crystal structure. Aluminum is a typical trivalent element and its valence does not change, so the lithium around aluminum is not easy to migrate during charging and discharging. Therefore, aluminum and the lithium around it may be used as a support to suppress changes in the crystal structure. In addition, aluminum has the effect of suppressing the dissolution of the surrounding transition metal M and improving the continuous charging tolerance. In addition, the Al-O bond is stronger than the transition metal MO bond, so the oxygen around aluminum can be suppressed from leaving. Through the above effects, thermal stability is improved. Therefore, when aluminum is included as an added element, the safety when used in a secondary battery can be improved. In addition, a positive electrode active material 100 can be achieved that is not prone to crystal structure collapse even after repeated charging and discharging.

[0068] On the other hand, when the amount of aluminum is too large, there is a possibility that the insertion and extraction of lithium may be adversely affected. Therefore, it is preferable that an appropriate amount of aluminum is contained in the entire positive electrode active material 100 .

[0069] In addition, it is known that the oxide of titanium, one of the added elements, has super hydrophilicity. Therefore, by manufacturing the positive electrode active material 100 containing titanium oxide in the surface layer 100a, it sometimes has good wettability to a solvent with a higher polarity. When manufacturing a secondary battery, the positive electrode active material 100 has good contact with the interface of the electrolyte with a higher polarity, and sometimes the increase of the internal resistance can be suppressed.

[0070] In addition, by including phosphorus, which is one of the additive elements, in the surface layer portion 100a, the Li x When x in MO2 is small, short circuit can be suppressed, which is preferable. For example, it is preferable that the compound containing phosphorus and oxygen exists in the surface layer portion 100a. As a compound containing phosphorus and oxygen, there is lithium phosphate, for example.

[0071] When the positive electrode active material 100 contains phosphorus, hydrogen fluoride generated by decomposition of the electrolyte reacts with phosphorus to reduce the concentration of hydrogen fluoride in the electrolyte, which is preferable.

[0072] In the case where the electrolyte contains LiPF6, hydrogen fluoride is sometimes generated by hydrolysis. In addition, hydrogen fluoride is sometimes generated by the reaction of polyvinylidene fluoride (PVDF) used as a component of the positive electrode with an alkali. By reducing the concentration of hydrogen fluoride in the electrolyte, corrosion of the current collector and / or peeling of the film 104 described later can sometimes be suppressed. In addition, the reduction in adhesion caused by gelation and / or insolubility of PVDF can sometimes be suppressed.

[0073] When the positive electrode active material 100 contains phosphorus in addition to magnesium, x A state in which x in MO2 is small has extremely high stability and is therefore preferred.

[0074] When the positive electrode active material 100 has cracks, if phosphorus, more specifically, a compound containing phosphorus and oxygen, exists inside the positive electrode active material on the surface of the cracks, such as in the buried portion, the cracks may be inhibited from expanding.

[0075] Note that when the surface portion contains only a compound of an added element and oxygen, lithium is not easily inserted and removed, so it is not preferred. For example, a structure in which the surface portion contains only magnesium oxide and a solid solution of magnesium oxide and an oxide of a divalent transition metal M is not preferred. Therefore, the surface portion 100a needs to contain at least the transition metal M and also contain lithium during discharge to have a path for lithium insertion and removal.

[0076] In order to sufficiently ensure a path for insertion and extraction of lithium, the total number of atoms of the transition metal M in the surface layer portion 100 a is preferably larger than the total number of atoms of the additional element.

[0077] In addition, the concentration of a part of the added elements, especially magnesium and aluminum, in the surface layer is preferably higher than that in the inner 100c, but they are preferably also present irregularly and in small amounts in the inner 100c. When magnesium and aluminum are present at appropriate concentrations at the lithium position in the inner 100c, the layered rock salt type crystal structure is easily maintained as described above.

[0078] In addition, it is preferred that the crystal structure changes continuously from the inner portion 100 c to the surface due to the concentration gradient of the added element. Alternatively, it is preferred that the crystal orientations of the surface portion and the inner portion 100 c are substantially identical.

[0079] For example, it is preferred that the crystal structure changes continuously from the inner part 100c of the layered rock salt type to the surface and the surface layer part of the rock salt type or having both the characteristics of the rock salt type and the layered rock salt type. Alternatively, it is preferred that the orientation of the surface layer part of the rock salt type or having both the characteristics of the rock salt type and the layered rock salt type is roughly consistent with the orientation of the inner part 100c of the layered rock salt type.

[0080] In addition, in this specification, etc., the layered rock salt type crystal structure belonging to the space group R-3m possessed by the composite oxide containing lithium and transition metal M refers to the following crystal structure: having a rock salt type ion arrangement in which cations and anions are alternately arranged, and the transition metal and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also be included. Strictly speaking, the layered rock salt type crystal structure is sometimes a structure formed by deformation of the lattice of the rock salt type crystal.

[0081] In addition, the rock salt type crystal structure has a cubic crystal structure such as space group Fm-3m, in which cations and anions are arranged alternately. In addition, vacancies of cations or anions may also be included.

[0082] In addition, whether or not the crystal has the characteristics of both the layered rock salt type crystal structure and the rock salt type crystal structure can be determined by electron diffraction, TEM images, cross-sectional STEM images, and the like.

[0083] There is no difference in the position of cations in the rock salt type crystal structure, but in the layered rock salt type crystal structure, there are two types of cation positions, one is the position where lithium occupies most of the position and the other is the position where transition metals occupy. Both the rock salt type and the layered rock salt type have a stacked structure in which the two-dimensional planes of cations and the two-dimensional planes of anions are arranged alternately. Among the bright spots in the electron diffraction pattern of the crystal plane forming the above-mentioned two-dimensional plane, when the central spot (transmitted spot) is taken as the origin 000, the bright spot closest to the central spot is, for example: the bright spot of the (111) plane of the ideal rock salt type crystal structure or the bright spot of the (003) plane of the ideal layered rock salt type crystal structure. For example, when comparing the electron diffraction patterns of rock salt type MgO and layered rock salt type LiMO2, the bright spot of the (003) plane of LiMO2 is about half the distance of the bright spot of the (111) plane of MgO. Therefore, for example, when the analysis region includes two phases of rock salt type MgO and layered rock salt type LiMO2, there are plane orientations in which bright spots of stronger brightness and bright spots of weaker brightness are arranged alternately in the electron diffraction pattern. Bright spots common to the rock salt type and the layered rock salt type have high brightness, while bright spots occurring only in the layered rock salt type have low brightness.

[0084] In addition, in cross-sectional STEM images, when observing the layered rock salt type crystal structure from a direction perpendicular to the c-axis, layers with higher brightness and layers with lower brightness are observed alternately. The positions of the cations of the rock salt type are not different, so the above characteristics are not observed. When a crystal structure having characteristics of both the rock salt type and the layered rock salt type is adopted, when observing from a specific crystal orientation, layers with higher brightness and layers with lower brightness are observed alternately in cross-sectional STEM images, and a metal having an atomic number greater than lithium exists in a part of the lower brightness layer, that is, the lithium layer.

[0085] The anions of the layered rock salt type crystal and the rock salt type crystal form a cubic closest packing structure (face-centered cubic lattice structure) respectively. Therefore, when the layered rock salt type crystal and the rock salt type crystal are in contact, there are crystal planes with the same orientation of the cubic closest packing structure formed by the anions.

[0086] Alternatively, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock salt type has a rhombus structure belonging to the space group R-3m, but in order to facilitate the understanding of the structure, it is usually expressed as a composite hexagonal lattice, and the (0001) plane of the layered rock salt type has a hexagonal lattice. The triangular lattice of the {111} plane of the cubic crystal has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock salt type. The state in which the lattices of the two are integrated can be said to be a state in which the orientation of the cubic closest packing structure is consistent.

[0087] Note that the space group of the layered rock salt type crystal is R-3m, which is different from the space group Fm-3m (the space group of the general rock salt type crystal) of the rock salt type crystal, so the Miller index of the crystal plane that satisfies the above conditions is different between the layered rock salt type crystal and the rock salt type crystal. In this specification, sometimes the state of the orientation of the cubic closest packing structure formed by the anions in the layered rock salt type crystal and the rock salt type crystal refers to the state of roughly consistent crystal orientation. In addition, the state of having a three-dimensional structural similarity or the same orientation in crystallography with roughly consistent crystal orientation is called topological derivative (topotaxy).

[0088] Whether the crystal orientations of two regions are roughly consistent can be determined by using TEM (Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM), ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope), electron diffraction patterns, TEM images, and FFT patterns of STEM images, etc. In addition, X-ray diffraction (XRD), electron diffraction, neutron diffraction, etc. can be used as a basis for determination.

[0089] Figure 2 An example of a TEM image showing that the orientations of the layered rock salt type crystals LRS and the rock salt type crystals RS are substantially consistent is shown. TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc. can be used to obtain images reflecting the crystal structure.

[0090] For example, the contrast derived from the crystal plane can be obtained from the high-resolution images of TEM. Due to the diffraction and interference of the electron beam, for example, when the electron beam is incident on the c-axis perpendicular to the layered rock salt type composite hexagonal lattice, the repetition of high contrast bands (bright band lines) and dark bands (dark band lines) derived from the (0003) plane can be obtained. Therefore, the repetition of bright lines and dark lines is observed in the TEM image, and between the bright lines (for example, Figure 2 L RS and L LRS When the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can be judged that the crystal planes are roughly consistent, that is, the crystal orientations are roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the orientations of the crystals are roughly consistent.

[0091] In addition, in the HAADF-STEM image, a contrast ratio proportional to the atomic number is obtained, and the larger the atomic number of the element, the brighter it is observed. For example, when using a layered rock salt type nickel-manganese-cobalt oxide belonging to the space group R-3m, the atomic number of the transition metal M, specifically, manganese (atomic number 25), cobalt (atomic number 27) and nickel (atomic number 28) is large, so the electron beam is more strongly scattered at the positions of these atoms, thereby observing the arrangement of the transition metal M atoms as bright lines or high-brightness points. Therefore, when observing the nickel-manganese-cobalt oxide having a layered rock salt type crystal structure in the direction perpendicular to the c-axis of the layered rock salt type crystal structure belonging to the space group R-3m, the arrangement of the transition metal M atoms is observed as bright lines or higher brightness points in the direction perpendicular to the c-axis, and the arrangement of lithium atoms and oxygen atoms is observed as dark lines or areas with lower brightness. The same is true when fluorine (atomic number: 9) and magnesium (atomic number: 12) are contained as additive elements of lithium nickel-manganese-cobalt oxide.

[0092] Therefore, in the HAADF-STEM image, the repetition of bright and dark lines is observed in two regions with different crystal structures. When the angle between the bright lines is less than 5 degrees or less than 2.5 degrees, it can be judged that the atomic arrangement is roughly consistent, that is, the crystal orientation is roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the orientation of the crystal is roughly consistent.

[0093] In addition, in ABF-STEM, the smaller the atomic number, the brighter the element is observed, but the contrast corresponding to the atomic number can be obtained in the same way as HAADF-STEM, so the orientation of the crystal can be determined in the same way as the HAADF-STEM image.

[0094] Figure 3A An example of a STEM image showing that the orientations of the layered rock salt type crystals LRS and the rock salt type crystals RS are substantially consistent with each other. Figure 3B The FFT pattern of the region showing rock salt type crystal RS, Figure 3C FFT pattern showing a region of layered rock-salt type crystalline LRS. Figure 3B and Figure 3C The composition, the card number of JCPDS and the d value and angle to be calculated later are shown on the left side. The measured value is shown on the right side. The spot with O is the zero-order diffraction. The example of lithium cobalt oxide and cobalt oxide is shown here, but one embodiment of the present invention is not limited to this. For example, nickel-manganese-lithium cobalt oxide and nickel oxide, manganese oxide and / or cobalt oxide can also be estimated to have roughly the same orientation.

[0095] exist Figure 3B The spots marked with A in the figure come from the 11-1 reflection of the cubic crystal. Figure 3C The spots marked with A in the figure are from the 0003 reflection of the layered rock salt type. Figure 3B and Figure 3C It can be seen that the orientation of the 11-1 reflection of the cubic crystal is roughly consistent with the orientation of the 0003 reflection of the layered rock salt type. Figure 3B The straight line of AO and the Figure 3C The straight lines of AO are roughly parallel. The "roughly consistent" and "roughly parallel" described here refer to the case where the angle is less than 5 degrees or less than 2.5 degrees.

[0096] As described above, in the FFT pattern and the electron diffraction pattern, when the orientations of the layered rock salt type crystals and the rock salt type crystals are substantially the same, the layered rock salt type crystals may be <0003> The orientation is roughly consistent with the <11-1> orientation of the rock salt type. At this time, their reciprocal points are preferably spot-shaped, that is, not continuous with other reciprocal points. The reciprocal points are spot-shaped and not continuous with other reciprocal points, which means that the crystallinity is high.

[0097] In addition, as described above, when the orientation of the 11-1 reflection of the cubic crystal is roughly the same as the orientation of the 0003 reflection of the layered rock salt type, a spot that does not originate from the 0003 reflection of the layered rock salt type is sometimes observed in a reciprocal space different from the orientation of the 0003 reflection of the layered rock salt type, depending on the incident orientation of the electron beam. Figure 3C The spot with B in the figure is from the 1014 reflection of the layered rock salt type. This spot is sometimes at the reciprocal point ( Figure 3C A) is 52° to 56° (i.e., ∠AOB is 52° to 56°) and d is 0.19nm to 0.21nm. Note that the above index is only an example and does not necessarily need to be consistent with the index. For example, the equivalent reciprocal grid points in 0003 or 1014 can also be used.

[0098] Similarly, a spot not derived from the 11-1 reflection of a cubic crystal is sometimes observed in a reciprocal space different from the orientation at which the 11-1 reflection of a cubic crystal is observed. Figure 3B The spots in the figure are from the 200 reflection of the cubic crystal. Sometimes, the reflections of 11-1 ( Figure 3B The diffraction spots are observed at locations where the difference in azimuth between A and B is greater than 54° and less than 56° (i.e., ∠AOB is greater than 54° and less than 56°). Note that the above index is only an example and does not necessarily need to be consistent with the index. For example, equivalent reciprocal grid points in 11-1 or 200 may also be used.

[0099] Note that when the orientation of the crystal is to be determined, it is preferred to thin the sample so that the (0003) plane of the layered rock salt type can be easily observed. Therefore, in TEM, it is preferred to thin the sample using FIB, etc. so that the electron beam is incident at [12-10]. It is known that positive electrode active materials of layered rock salt type such as LiMO2 (M is at least one of Ni, Co, and Mn) tend to present as crystal planes on the (0003) plane and its equivalent plane, and on the (10-14) plane and its equivalent plane. Therefore, when carefully observing the shape of the positive electrode active material using SEM, etc., the sample can be thinned so that the (0003) plane can be easily observed in TEM, etc.

[0100] < <xps>> X-ray photoelectron spectroscopy (XPS) can analyze the depth range of about 2nm to 8nm (generally less than 5nm) from the surface when analyzing inorganic oxides and using monochromated aluminum Kα line as the X-ray source, so the concentration of each element in about half of the depth direction of the surface part 100a can be quantitatively analyzed. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed. Note that the quantitative accuracy of XPS is about ±1 atomic% in many cases. Although it depends on the element, the detection limit is about 1 atomic%.

[0101] In the positive electrode active material 100 of one embodiment of the present invention, the concentration of one or more selected from the added elements in the surface portion is preferably higher than the concentration in the inner portion 100c. That is, the concentration of one or more selected from the added elements in the surface portion is preferably higher than the average concentration of the positive electrode active material 100 as a whole. Therefore, for example, it can be said that the concentration of one or more selected from the added elements in the surface portion measured by XPS or the like is preferably higher than the average concentration of the positive electrode active material 100 as a whole measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry analysis). For example, the magnesium concentration of at least a portion of the surface portion 100a measured by XPS or the like is preferably higher than the magnesium concentration of the positive electrode active material 100 as a whole. In addition, the aluminum concentration of at least a portion of the surface portion 100a is preferably higher than the aluminum concentration of the positive electrode active material 100 as a whole.

[0102] Note that the surface and surface layer of the positive electrode active material 100 of one embodiment of the present invention do not include carbonates, hydroxyls, etc. chemically adsorbed after the positive electrode active material 100 is manufactured as described above. In addition, it does not include electrolytes, adhesives, conductive materials, or compounds derived from them attached to the surface of the positive electrode active material 100. Therefore, when quantifying the elements contained in the positive electrode active material, the following correction can also be performed, that is, removing carbon, hydrogen, excess oxygen, excess fluorine, etc. that may be detected by surface analysis such as XPS. For example, XPS can identify the type of bonding by analysis, and can also perform corrections to remove CF bonds derived from the adhesive.

[0103] In addition, the samples of the positive electrode active material and the positive electrode active material layer can be washed before various analyses to remove the electrolyte, adhesive, conductive material or compounds derived from them attached to the surface of the positive electrode active material. At this time, sometimes lithium is dissolved in the solvent used for washing, but the added element is not easy to dissolve, so it has no effect on the atomic number ratio of the added element.

[0104] When performing XPS analysis, for example, monochromatized aluminum Kα rays are used as an X-ray source. In addition, for example, the extraction angle may be 45°. For example, the measurement may be performed with the following apparatus and conditions. Measuring device: Quantera II manufactured by PHI X-ray source: monochromated aluminum Kα (1486.6 eV) Detection area: 100μmφ Detection depth: about 4nm to 5nm (extraction angle is 45°) Measurement spectrum: wide scan, narrow scan for each detected element

[0105] < <edx>> It is preferred that one or two of the additional elements and the transition metal M included in the positive electrode active material 100 have a concentration gradient. In addition, the positive electrode active material 100 is more preferably different in depth from the surface according to the concentration peak of the added element. The concentration gradient of the added element and the transition metal M can be evaluated by, for example, exposing the cross section of the positive electrode active material 100 by FIB (Focused Ion Beam) or the like and analyzing the cross section using energy dispersive X-ray spectrometry (EDX), EPMA (electron probe microanalysis), or the like.

[0106] In EDX measurement, the method of measuring while scanning in a region for two-dimensional evaluation is called EDX surface analysis. In addition, the method of evaluating the atomic concentration distribution in the positive electrode active material by linear scanning and measurement is called line analysis. In addition, the method of extracting the data of the linear region from the surface analysis of EDX is sometimes called line analysis. In addition, the method of measuring a certain region without scanning is called point analysis.

[0107] By EDX surface analysis (e.g., element mapping), the concentration of the added element and transition metal M in the surface layer, the interior 100c, and the vicinity of the grain boundary 101 of the positive electrode active material 100 can be quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. In addition, in the analysis of thinning the sample such as STEM-EDX, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.

[0108] Therefore, when the positive electrode active material 100 of one embodiment of the present invention is subjected to EDX surface analysis or EDX point analysis, the concentration of each added element in the surface portion is preferably higher than the concentration of each added element in the inner portion 100c. In addition, the concentration of at least one selected from cobalt and manganese in the transition metal M in the surface portion is preferably higher than the concentration of the element in the inner portion 100c. Similarly, the nickel concentration in the inner portion 100c is preferably higher than the nickel concentration in the surface portion.

[0109] For example, when EDX surface analysis or EDX point analysis is performed on the positive electrode active material 100 containing magnesium and / or aluminum as additive elements, the magnesium and / or aluminum concentration in the surface portion is preferably higher than that in the inner portion 100 c.

[0110] In addition, the surface of the positive electrode active material 100 is preferably smooth and less uneven, but it is not necessarily necessary for the entire positive electrode active material 100 to be smooth and less uneven. In a composite oxide having a layered rock salt type crystal structure belonging to R-3m, sliding is likely to occur on a surface parallel to the (001) surface, such as a surface where lithium is arranged. For example, Figure 4A As shown, when there is a (001) plane, through a process such as pressing, sometimes Figure 4B As shown by the arrow in the figure, the material slides and deforms in a direction parallel to the (001) plane.

[0111] In this case, in the surface newly generated by sliding and its surface layer portion 100 a , the added element may not exist or be below the detection limit. Figure 4B EF in FIG. 1 shows an example of a surface newly generated by sliding and its surface layer portion 100a and surface layer portion 100b.

[0112] However, sliding easily occurs in a direction parallel to the (001) plane, so the newly generated surface and its surface layer 100a are easily oriented (001). At this time, the diffusion path of lithium ions is not exposed and is relatively stable, so there is almost no problem even if the added element does not exist or is below the detection limit.

[0113] As described above, in a layered rock salt type composite oxide whose composition is LiMO2 and whose crystal structure belongs to R-3m, the transition metal M is arranged parallel to the (001) plane. In addition, in the HAADF-STEM image, the brightness of cobalt, which has the largest atomic number in LiMO2, is the highest. Therefore, in the HAADF-STEM image, the arrangement of atoms with high brightness can be regarded as the arrangement of the transition metal M. The repetition of this arrangement with high brightness is synonymous with crystal stripes or lattice stripes.

[0114] Furthermore, the positive electrode active material 100 may have a coating on at least a portion of the surface. Figure 5A , Figure 5B and Figure 5C An example of a positive electrode active material 100 having a coating 104 is shown.

[0115] For example, the coating 104 is preferably a film formed by the deposition of decomposition products of the electrolyte as the charge and discharge proceeds. By having a coating derived from the electrolyte on the surface of the positive electrode active material 100, it can be expected that the charge and discharge cycle characteristics will be improved. This is because of the following reasons: suppressing the rise in impedance on the surface of the positive electrode active material; or suppressing the dissolution of the transition metal M; etc. The coating 104 preferably contains carbon, oxygen and fluorine, for example. In addition, a high-quality coating is easily obtained in the case where LiBOB and / or SUN (Suberonitrile) is used as part of the electrolyte. Therefore, a coating 104 containing one or more selected from boron, nitrogen, sulfur and fluorine is sometimes a high-quality coating, so it is preferred. In addition, the coating 104 may not cover the entire positive electrode active material 100.

[0116] This embodiment mode can be implemented in combination with other embodiment modes.

[0117] (Implementation Method 2) In this embodiment, refer to Figures 6 to 9 An example of a method for producing the positive electrode active material 100 according to one embodiment of the present invention will be described.

[0118] In order to produce the positive electrode active material 100 having the distribution, composition and / or crystal structure of the additive element as described in the above embodiment, the method of adding the additive element is important.

[0119] Therefore, in the manufacturing process of the positive electrode active material 100, it is preferred to first synthesize nickel-manganese-cobalt lithium oxide having a large crystal grain size, and then mix and add element sources and perform heat treatment.

[0120] In order to synthesize lithium nickel-manganese-cobalt oxide having a large grain size, it is effective to perform the steps of adding a lithium source and heating multiple times.

[0121] In addition, in the method of synthesizing by mixing a nickel source, a manganese source, a cobalt source or a lithium source with an additive element source at the same time, it is not easy to increase the concentration of the additive element in the surface layer. In addition, when only the additive element source is mixed without heating after synthesizing nickel-manganese-cobalt lithium, the additive element only adheres to the nickel-manganese-cobalt lithium and does not dissolve in the nickel-manganese-cobalt lithium. Unless fully heated, it is not easy to distribute the additive element well. Therefore, it is preferred that the additive element source is mixed after synthesizing nickel-manganese-cobalt lithium for heat treatment. Sometimes the heat treatment after the mixed additive element source is called annealing.

[0122] <<Method 1 for producing positive electrode active material>> Reference Figure 6 and Figure 7 A method 1 for producing the positive electrode active material 100 will be described.

[0123] <Step S11> As Figure 6 In step S11, firstly, a transition metal M source, namely a nickel source (Ni source), a cobalt source (Co source) and a manganese source (Mn source) is prepared. The mixing ratio of nickel, cobalt and manganese is preferably within a range that can have a layered rock salt type crystal structure.

[0124] In particular, when the transition metal M included as the positive electrode active material 100 contains more nickel, the raw material sometimes becomes cheaper than when there is more cobalt, and the charge and discharge capacity per unit weight is sometimes increased, so it is preferred. For example, the nickel ratio in the transition metal M is preferably more than 50 atomic%, more preferably more than 60 atomic%, and further preferably more than 75 atomic%. However, when the proportion of nickel is too high, there is a concern that chemical stability and heat resistance are reduced. Therefore, the nickel in the transition metal M is preferably less than 95 atomic%.

[0125] When cobalt is included as the transition metal M, the average discharge voltage is high and cobalt contributes to the stabilization of the layered rock salt structure, thereby realizing a highly reliable secondary battery, so it is preferred. However, cobalt is more expensive than nickel and manganese and is unstable, so when the proportion of cobalt is too high, there is a concern that the manufacturing cost of the secondary battery will increase. Therefore, for example, the cobalt in the transition metal M is preferably 2.5 atomic % or more and 34 atomic % or less.

[0126] Note that the transition metal M does not necessarily need to contain cobalt.

[0127] When manganese is included as the transition metal M, heat resistance and chemical stability are improved, so it is preferred. However, when the proportion of manganese is too high, there is a tendency for the discharge voltage and discharge capacity to decrease. Therefore, for example, manganese in the transition metal M is preferably 2.5 atomic % or more and 34 atomic % or less.

[0128] Note that manganese does not necessarily need to be contained as the transition metal M.

[0129] The transition metal M source is prepared as an aqueous solution containing the transition metal M. As a nickel source, an aqueous solution of a nickel salt can be used. As a nickel salt, for example, nickel sulfate, nickel chloride, nickel nitrate or a hydrate thereof can be used. In addition, an organic acid salt of nickel such as nickel acetate or a hydrate thereof can also be used. In addition, as a nickel source, an aqueous solution of a nickel alkoxide or an organic nickel complex can also be used. Note that in this specification, etc., an organic acid salt refers to a compound of an organic acid such as acetic acid, citric acid, oxalic acid, formic acid, butyric acid and a metal.

[0130] Similarly, a cobalt salt aqueous solution can be used as a cobalt source. As the cobalt salt, for example, cobalt sulfate, cobalt chloride, cobalt nitrate or their hydrates can be used. In addition, organic acid salts of cobalt such as cobalt acetate or their hydrates can also be used. In addition, as the cobalt source, an aqueous solution of a cobalt alkoxide or an organic cobalt complex can be used.

[0131] Similarly, as a manganese source, a manganese salt aqueous solution can be used. As a manganese salt, for example, manganese sulfate, manganese chloride, manganese nitrate or their hydrates can be used. In addition, as a manganese salt, an organic acid salt of manganese such as manganese acetate or their hydrates can also be used. In addition, as a manganese source, an aqueous solution of a manganese alkoxide or an organic manganese complex can be used.

[0132] In this embodiment, an aqueous solution of nickel sulfate, cobalt sulfate and manganese sulfate dissolved in pure water is prepared as a source of transition metal M. At this time, the atomic ratio of nickel, cobalt and manganese is Ni:Co:Mn=8:1:1 or thereabouts. The aqueous solution is acidic.

[0133] <Step S13> In addition, if Figure 6 As shown in step S13, a chelating agent may also be prepared. As a chelating agent, for example, glycine, oxine, 1-nitroso-2-naphthol, 2-mercaptobenzothiazole or EDTA (ethylenediaminetetraacetic acid) may be cited. In addition, a variety selected from glycine, oxine, 1-nitroso-2-naphthol or 2-mercaptobenzothiazole may also be used. At least one of them is dissolved in pure water and used as a chelating aqueous solution. A chelating agent is a complexing agent that forms a chelating compound and is more preferred than a general complexing agent. Of course, a complexing agent may also be used instead of a chelating agent, and ammonia water may be used as a complexing agent. By using a chelating aqueous solution, the generation of unnecessary crystal nuclei can be suppressed and crystal growth can be promoted, so it is preferred. When the generation of unnecessary nuclei is suppressed, the generation of microparticles is suppressed, so a composite hydroxide with excellent particle size distribution can be obtained. In addition, by using a chelating aqueous solution, the acid-base reaction can be delayed, and secondary particles that are almost spherical can be obtained because the reaction proceeds gradually. Glycine has the function of maintaining a constant pH value at a pH of 9 to 10 or thereabouts. By using a glycine aqueous solution as the chelating aqueous solution, it is easy to control the pH of the reaction tank when obtaining the above-mentioned composite hydroxide 98, so it is preferred.

[0134] <Step S14> Then, as Figure 6 In step S14, a transition metal M source and a chelating agent are mixed to produce an acid solution.

[0135] <Step S21> Then, as Figure 6 In step S21, an alkaline solution is prepared. As the alkaline solution, for example, an aqueous solution containing sodium hydroxide, potassium hydroxide, lithium hydroxide or ammonia can be used. An aqueous solution obtained by dissolving them in pure water can be used. Alternatively, an aqueous solution obtained by dissolving a plurality of selected from sodium hydroxide, potassium hydroxide, lithium hydroxide and ammonia in pure water can be used.

[0136] Pure water suitable for the above transition metal M source and alkaline solution is water with a resistivity of 1MΩ·cm or more, more preferably water with a resistivity of 10MΩ·cm or more, and further preferably water with a resistivity of 15MΩ·cm or more. Water that meets the above resistivity has a high purity and contains very few impurities.

[0137] <Step S22> In addition, if Figure 6 As shown in step S22, water is preferably prepared in the reaction tank. The water can be an aqueous solution of a chelating agent, more preferably pure water. Using pure water can promote nucleation, thereby making a small-particle composite hydroxide. The water prepared in the reaction tank can also be called a pre-stored solution or adjustment solution of the reaction tank. When a chelating aqueous solution is used, the record of step S13 can be referred to.

[0138] <Step S31> Then, as Figure 6 In step S31, the acid solution and the alkaline solution are mixed to react with each other. This reaction can be said to be a coprecipitation reaction, a neutralization reaction or an acid-base reaction.

[0139] In the coprecipitation reaction of step S31, the pH of the reaction system is preferably 9.0 or more and 11.5 or less.

[0140] For example, when alkaline solution is placed in the reaction tank and acid solution is dripped in the reaction tank, the pH of the aqueous solution in the reaction tank is preferably maintained within the scope of the above-mentioned conditions. In addition, it is also the same when alkaline solution is dripped into the reaction tank in which the acid solution is placed. When the solution in the reaction tank is more than 200mL and below 350mL, the dripping speed of the acid solution or the alkaline solution is preferably below 0.01mL / minute, which is easy to control the pH condition. The reaction tank includes a reaction vessel etc.

[0141] In the reaction tank, a stirring unit is used to stir the aqueous solution. The stirring unit includes an agitator or a stirring wing, etc. The stirring wing can be provided with more than two and less than six. For example, when four stirring wings are adopted, the stirring wing is configured in a cross-shaped manner when viewed from above. The rotating speed of the stirring unit is more than 800rpm and less than 1200rpm. In addition, a baffle plate can also be provided in the reaction tank to change the stirring direction and flow velocity. By providing a baffle plate, the mixing efficiency can be improved, and thus particles of a composite hydroxide of a more uniform size can be synthesized.

[0142] The temperature of the reaction bath is preferably adjusted to 50° C. or higher and 90° C. or lower. The dropping of the alkaline solution or the acid solution may be started after the reaction bath reaches this temperature.

[0143] In addition, the atmosphere in the reaction cell is preferably an inert atmosphere. In this case, nitrogen or argon can be used as the inert atmosphere. In the case of a nitrogen atmosphere, nitrogen gas can be introduced at a flow rate of 0.5 L / min or more and 2 L / min or less.

[0144] In addition, a reflux cooler may be provided in the reaction pool, and the reflux cooler can release nitrogen gas from the reaction pool and return water vapor to the reaction pool.

[0145] Through the above-described coprecipitation reaction, a composite hydroxide 98 containing a transition metal M is precipitated.

[0146] <Step S32> In order to recover the composite hydroxide 98, it is preferred that Figure 6 Filtration is performed as shown in step S32. Filtration is preferably performed by suction filtration. When filtering, an organic solvent (such as acetone, etc.) may be used after washing the reaction product precipitated in the reaction tank with pure water.

[0147] <Step S33> like Figure 6 As shown in step S33, the filtered composite hydroxide 98 is preferably dried. For example, it is dried for 0.5 hours to 20 hours under vacuum at 60°C to 200°C. For example, it can be dried for 12 hours. In this way, the composite hydroxide 98 can be obtained.

[0148] In this way, a composite hydroxide 98 containing the transition metal M can be obtained. In this specification, etc., the composite hydroxide 98 refers to hydroxides of a plurality of metals. The composite hydroxide 98 can be said to be a precursor inside the positive electrode active material 100 .

[0149] <Step S41> Then, as Figure 7 In step S41, a lithium source is prepared. At this time, since the steps of adding the lithium source and heating are performed multiple times, the amount of lithium prepared in step S41 is less than the final amount of lithium. For example, assuming that the sum of the number of atoms of nickel, cobalt, and manganese is 1, the lithium can be set to be greater than 0.5 and less than 0.9 (atomic number ratio), and more preferably set to 0.7 (atomic number ratio).

[0150] As a lithium source, for example, lithium hydroxide, lithium carbonate or lithium nitrate can be used. It is particularly preferred to use a material with a lower melting point among lithium compounds, such as lithium hydroxide (melting point 462°C). Because positive electrode active materials with a higher proportion of nickel are more prone to cation mixing than lithium cobalt oxide, it is necessary to perform heating in step S43 at a low temperature. Therefore, it is preferred to use a material with a lower melting point.

[0151] In addition, the smaller the particle size of the lithium source is, the better the reaction can be promoted, so it is preferred. For example, a lithium source micronized by a fluidized bed jet mill can be used. Here, the particle size refers to the median particle size.

[0152] <Step S42> Then, as Figure 7 In step S42, the composite hydroxide 98 is mixed with a lithium source. The mixing can be performed by a dry method or a wet method. In the mixing, for example, a ball mill, a sand mill, etc. can be used. When a ball mill is used, for example, zirconia balls are preferably used as the medium. In addition, when a ball mill or a sand mill is used, in order to suppress contamination from the medium or material, the circumferential speed is preferably set to be greater than 100 mm / second and less than 2000 mm / second. The cobalt compound and the lithium compound are sometimes crushed while mixing.

[0153] <Step S43> Next, the mixture of the composite hydroxide 98 and the lithium source is heated. To distinguish it from other heating steps, Figure 7 In some cases, step S43 is referred to as the first heating, step S53 is referred to as the second heating, and step S55 is referred to as the third heating.

[0154] As a roasting device for the above-mentioned heating, a muffle furnace, a roller kiln or a rotary kiln can be used. The crucible, sagger, push plate and container used for heating are preferably made of a material that is not easy to release impurities. For example, a crucible of 99.9% pure aluminum oxide can be used. In mass production, for example, a sagger of mullite-cordierite (Al2O3·SiO2·MgO) can be used.

[0155] The heating temperature in step S43 is preferably 400° C. to 750° C., more preferably 650° C. to 750° C. The heating time in step S43 is preferably 1 hour to 30 hours, more preferably 2 hours to 20 hours.

[0156] The heating atmosphere is preferably an oxygen-containing atmosphere or an oxygen-containing atmosphere with little moisture such as so-called dry air (for example, a dew point of -50°C or lower, preferably -80°C or lower).

[0157] In addition, as step S44, it is preferred to perform a grinding process after heating. The grinding can be performed using a mortar, for example. Furthermore, classification can also be performed using a sieve. By having a grinding process, the particle size and / or shape of the positive electrode active material 100 can be made more uniform. Through the above process, a composite oxide is obtained (step S45).

[0158] <Step S51> Next, as step S51, a lithium source is prepared. At this time, the lithium source is prepared in such a way that the total amount of lithium prepared in step S41 and step S51 becomes the final required amount of lithium. For example, assuming that the sum of the number of atoms of nickel, cobalt and manganese in step S41 is 1 and lithium is set to 0.7 (atomic number ratio), in step S51, for example, 0.31 (atomic number ratio) of lithium is preferably prepared. Here, it is assumed that the final amount of lithium is set to 1.01 (atomic number ratio) when the sum of the number of atoms of nickel, cobalt and manganese is 1, but one embodiment of the present invention is not limited to this. Assuming that the sum of the number of atoms of nickel, cobalt and manganese is 1, the final amount of lithium is preferably greater than 0.95 and less than 1.25 (atomic number ratio), and more preferably greater than 1.00 and less than 1.10 (atomic number ratio). In addition to the amount of lithium source prepared, the record of step S41 can be referred to.

[0159] Note that although Figure 7 The method of adding the lithium source twice, that is, step S41 and step S51, and heating them separately is described in the above description, but one embodiment of the present invention is not limited thereto. The lithium source may also be added three or more times and heated separately.

[0160] <Step S52> Next, the composite oxide obtained in step S45 and the lithium source are mixed. The mixing can refer to the description of step S42.

[0161] <Step S53> Next, the mixture of the composite oxide 98 and the lithium source is heated. The heating in step S53 is preferably performed at a sufficiently high temperature in order to increase the crystal size of the positive electrode active material 100 , but the range may vary depending on the composition of the transition metal M.

[0162] When the proportion of nickel in the transition metal M is high, such as 70% or more, the heating temperature is preferably 750°C or more, more preferably 800°C or more, and further preferably 850°C or more. However, too high a temperature may cause the transition metal M such as nickel to be reduced to a divalent state. Therefore, the heating temperature is preferably 950°C or less, more preferably 920°C or less, and further preferably 900°C or less.

[0163] When the ratio of nickel in the transition metal M is 40% or more and 70% or less, the heating temperature is preferably 900° C. or more, more preferably 950° C. or more, and further preferably about 970° C. However, too high a temperature may cause the same disadvantages as described above, so it is preferably 1020° C. or less, and more preferably 990° C. or less. For other heating conditions, refer to the description of step S43.

[0164] In addition, as step S54, it is preferable to perform a grinding process after heating. The grinding process can refer to the description of step S44.

[0165] <Step S55> Furthermore, it is more preferred to perform heating in step S55. By performing this heating, the residue of the lithium source and the like can be reduced. The heating temperature of step S55 is preferably 400°C or more and 900°C or less, more preferably 750°C or more and 850°C or less. In addition, the heating time of step S52 is preferably 1 hour or more and 30 hours or less, more preferably 2 hours or more and 20 hours or less. However, heating in step S55 may not be performed. For other heating conditions, refer to the description of step S43.

[0166] In addition, as step S56, it is preferable to perform a grinding process after heating. The grinding process can refer to the description of step S44.

[0167] in addition, Figure 7 The method described above is to perform heating twice in step S53 and step S55 after mixing the lithium source in step S51, but one embodiment of the present invention is not limited thereto. Heating may be performed three or more times.

[0168] Through the above steps, the positive electrode active material 100 can be manufactured.

[0169] <<Method for producing positive electrode active material 2>> Will refer to Figure 6 and Figure 8 The following describes a method 2 for producing the positive electrode active material 100. The positive electrode active material 100 produced by the production method 2 includes an additive element. The following mainly describes the steps different from the production method 1, and the description of the production method 1 can be referred to for other steps.

[0170] <Step S71> As Figure 8 In step S71, prepare to add an element source.

[0171] In addition, as the additive element, for example, one or more selected from magnesium, aluminum, calcium, titanium, zirconium, fluorine, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine and beryllium can be used.

[0172] As the magnesium source, for example, an organic compound containing magnesium, such as magnesium fluoride, magnesium hydroxide, magnesium carbonate, magnesium acetylacetonate (dihydrate), magnesium lactate, and magnesium phthalocyanine (II), can be used.

[0173] As the aluminum source, for example, an organic compound containing aluminum, such as aluminum hydroxide, aluminum fluoride, aluminum alkoxide, aluminum acetylacetonate, and aluminum lactate, can be used.

[0174] <Step S72> The above-mentioned additive element source and the composite oxide having a large crystal grain size obtained by the same steps as in the production method 1 are mixed.

[0175] Note that in this embodiment, the manufacturing method of mixing the additive element in step S72 is described, but one aspect of the present invention is not limited to this. The additive element may also be mixed in other processes. For example, the lithium source and the additive element may also be mixed simultaneously in step S42 and step S52. In addition, the transition metal M source and the additive element may also be mixed simultaneously in step S14.

[0176] <Step S73> Next, the added element source and the composite oxide are heated. The heating temperature of step S73 is preferably 400°C to 900°C, more preferably 750°C to 850°C. In addition, the heating time of step S73 is preferably 0.5 hours to 30 hours, more preferably 1 hour to 10 hours. For other heating conditions, refer to the description of step S43.

[0177] In addition, as step S74, it is preferable to perform a grinding process after heating. The grinding process can refer to the description of step S44.

[0178] Through the above steps, the positive electrode active material 100 can be manufactured (step S75 ).

[0179] <<Method for producing positive electrode active material 3>> Will refer to Figure 6 and Fig. 9 The manufacturing method 3 of the positive electrode active material 100 is described. The positive electrode active material 100 manufactured by the manufacturing method 3 includes an additive element, and the atomic number ratio of at least one element of cobalt and manganese in the surface layer is higher than the atomic number ratio of the element in the interior. The steps different from the manufacturing method 2 are mainly described, and the description of the manufacturing method 2 can be referred to for other steps.

[0180] <Step S61> As Fig. 9 In step S61, at least one of a cobalt source and a manganese source is prepared.

[0181] As the cobalt source, for example, an organic compound containing cobalt such as cobalt oxide, cobalt hydroxide, or cobalt alkoxide can be used.

[0182] As the manganese source, for example, an organic compound containing manganese, such as manganese oxide, manganese hydroxide, or manganese alkoxide, can be used.

[0183] Note that in step S61, a composite hydroxide may be prepared. For example, a composite hydroxide containing cobalt and manganese may be prepared as a cobalt source and a manganese source. In addition, a nickel-manganese-cobalt hydroxide may be prepared in which the proportion of nickel in the nickel-manganese-cobalt hydroxide is less than 10%. Figure 6 Composite hydroxides produced in.

[0184] <Step S62> At least one of the above-mentioned cobalt source and manganese source is mixed with a composite oxide having a large grain size obtained by the same process as manufacturing method 1. There is no particular restriction on the mixing method. For example, when the cobalt source and / or the manganese source is an alkoxide, a sol-gel method can be used. In addition, when the cobalt source and / or the manganese source is a composite hydroxide, a mechanochemical method can be used.

[0185] <Step S63> Next, the mixture of the cobalt source and / or manganese source and the composite oxide is heated.

[0186] In addition, as step S64, it is preferable to perform a grinding process after heating. The grinding process can refer to the description of step S44.

[0187] The composite oxide is produced through the above steps, and then the positive electrode active material 100 can be produced by mixing the added elements and heating them in the same manner as in the method 2 for producing the positive electrode active material.

[0188] Note that Figure 6 and Fig. 9 The method of adding at least one of the cobalt source and the manganese source before adding the additional element source is described in the above, but one embodiment of the present invention is not limited to this. At least one of the cobalt source and the manganese source may be added after adding the additional element source, or the additional element source and at least one of the cobalt source and the manganese source may be added at the same time. Figure 6 The composition of the transition metal M in the inner and surface parts is changed when the composite hydroxide 98 is prepared. At this time, for example, by changing from an acid solution with a high nickel ratio contained in the transition metal M to an acid solution with a low nickel ratio, the nickel ratio in the inner and surface parts can be changed.

[0189] This embodiment mode can be implemented in combination with other embodiment modes.

[0190] (Implementation 3) In this embodiment, each element constituting a lithium ion battery is described.

[0191] [positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and may further contain at least one of a conductive material and a binder. As the positive electrode active material, the material described in Embodiment 1 can be used.

[0192] Fig. 10A An example of a schematic diagram showing a cross section of a positive electrode is shown.

[0193] The positive electrode current collector 21 may be, for example, a metal foil. The positive electrode may be formed by applying a slurry on a metal foil and drying it. Alternatively, the slurry may be pressed after drying. In the positive electrode, an active material layer is formed on the positive electrode current collector 21.

[0194] The slurry is a material liquid used to form an active material layer on the positive electrode current collector 21, and contains an active material, a binder and a solvent, and preferably also contains a conductive material. The slurry is sometimes referred to as an electrode slurry or an active material slurry. The positive electrode slurry is used when forming a positive electrode active material layer, and is sometimes referred to as a negative electrode slurry when forming a negative electrode active material layer.

[0195] The positive electrode active material 100 has the function of absorbing lithium ions and releasing lithium ions accompanying charge and discharge. As a positive electrode active material 100 used in one embodiment of the present invention, a material with less degradation accompanying charge and discharge even when a high charging voltage is used. In this specification, etc., in the absence of special instructions, the charging voltage is expressed as a reference to the potential of lithium metal. In this specification, etc., a high charging voltage refers to, for example, a charging voltage of 4.5V or more, preferably 4.55V or more, more preferably 4.6V or more, further preferably 4.65V or more, and most preferably 4.7V or more.

[0196] As the positive electrode active material 100 used in one embodiment of the present invention, any material can be used as long as it is a material that has little deterioration accompanying charge and discharge even when a high charging voltage is used, and the materials described in Embodiment 1 or Embodiment 2 can be used. In addition, as long as the positive electrode active material 100 is a material that has little deterioration accompanying charge and discharge even when a high charging voltage is used, two or more materials with different particle sizes can be used.

[0197] Conductive materials are also called conductivity imparting agents or conductive aids, and carbon materials can be used. By attaching conductive materials between multiple active materials, multiple active materials are electrically connected to each other and the conductivity is improved. Note that in this specification, "attachment" not only refers to the physical close contact between the active material and the conductive material, but also refers to the concept of including the following situations: when covalent bonds occur; when bonded by van der Waals forces; when the conductive material covers a part of the surface of the active material; when the conductive material is embedded in the surface unevenness of the active material; when they are not in contact with each other but are electrically connected, etc.

[0198] Specific examples of carbon materials that can be used as the conductive material include carbon black (furnace black, acetylene black, etc.).

[0199] FIG. 10A to FIG. 10D An example of a positive electrode is shown.

[0200] Fig. 10A Carbon black 43 , which is an example of a conductive material, and an electrolyte 51 contained in the gaps between the positive electrode active materials 100 are shown, and an example is shown in which a second positive electrode active material 110 is contained in addition to the positive electrode active material 100 .

[0201] In order to fix the positive electrode current collector 21 and the active material such as metal foil, the positive electrode of the secondary battery can also be mixed with an adhesive (resin). Adhesive is also called a binder. Adhesive is a polymer material. When a large amount of adhesive is included, the proportion of active material in the positive electrode is reduced and the discharge capacity of the secondary battery is reduced. Therefore, it is preferred to mix the amount of adhesive to a minimum.

[0202] Fig. 10A The example in which the positive electrode active material 100 is spherical is shown, but there is no particular limitation on the shape. The cross-sectional shape of the positive electrode active material 100 may be, for example, an ellipse, a rectangle, a trapezoid, a triangle, a polygon with an arcuate corner, or an asymmetric shape. For example, Fig. 10B An example is shown in which the positive electrode active material 100 has a polygonal shape with rounded corners.

[0203] In addition, Fig. 10B In the positive electrode, graphene 42 is used as a carbon material used as a conductive material. Fig. 10B In the embodiment, a positive electrode active material layer including a positive electrode active material 100 , graphene 42 , and carbon black 43 is formed on the positive electrode current collector 21 .

[0204] Note that in the step of mixing the graphene 42 and the carbon black 43 to obtain the electrode slurry, the weight of the mixed carbon black is preferably 1.5 times or more and 20 times or less, and preferably 2 times or more and 9.5 times or less, that of the graphene.

[0205] When the mixing of graphene 42 and carbon black 43 is set within the above range, the dispersion stability of carbon black 43 is excellent when adjusting the slurry, and it is not easy to generate an aggregation part. In addition, when the mixing of graphene 42 and carbon black 43 is set within the above range, a high electrode density can be achieved compared to a positive electrode using only carbon black 43 as a conductive material. By increasing the electrode density, the capacity per unit weight can be increased. Specifically, the density of the positive electrode active material layer measured by weight can be 3.5 g / cc or more.

[0206] Compared with a positive electrode using only graphene as a conductive material, the electrode density is low, but the mixing of the first carbon material (graphene) and the second carbon material (acetylene black) is within the above range, thereby enabling correspondingly fast charging. Therefore, this is particularly effective when used for a vehicle-mounted secondary battery.

[0207] exist Fig. 10C , an example of a positive electrode using carbon fibers 44 instead of graphene is shown. Fig. 10C Shown with Fig. 10B Different example: By using carbon fiber 44, aggregation of carbon black 43 can be prevented and dispersibility can be improved.

[0208] Note that Fig. 10C In the figure, the region not filled with the positive electrode active material 100, the carbon fiber 44, and the carbon black 43 refers to a void or a binder.

[0209] Fig. 10D Other examples of positive electrodes are shown. Fig. 10C An example is shown in which carbon fibers 44 are used in addition to graphene 42. By using both graphene 42 and carbon fibers 44, aggregation of carbon black such as carbon black 43 can be prevented, and thus dispersibility can be further improved.

[0210] Note that Fig. 10D In the figure, the region not filled with the positive electrode active material 100, the carbon fiber 44, the graphene 42, and the carbon black 43 refers to a void or a binder.

[0211] The secondary battery can be manufactured by the following steps: FIG. 10A to FIG. 10D Any positive electrode in the above is stacked with a separator on the positive electrode, and the stacked body in which the negative electrode is stacked on the separator is placed in a container (an outer packaging body, a metal can, etc.) and the container is filled with an electrolyte.

[0212] <Adhesive> As the binder, for example, styrene-butadiene rubber (SBR) is preferably used. rubber), styrene-isoprene-styrene rubber As the adhesive, rubber materials such as propylene rubber, acrylonitrile-butadiene rubber, butadiene rubber, and ethylene-propylene-diene copolymer can also be used. Fluorine rubber can also be used as an adhesive.

[0213] In addition, as the binder, for example, a water-soluble polymer is preferably used. As the water-soluble polymer, for example, polysaccharides can also be used. As the polysaccharides, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, regenerated cellulose, starch, etc. can be used. It is more preferred to use these water-soluble polymers and the above-mentioned rubber material in combination.

[0214] Alternatively, as an adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.

[0215] As the binder, a plurality of the above-mentioned materials may be used in combination.

[0216] For example, materials with particularly good viscosity regulating effects can also be used in combination with other materials. For example, although rubber materials and the like have high cohesive force and high elasticity, it is sometimes difficult to regulate viscosity when mixed in a solvent. In such a case, for example, it is preferably mixed with materials with particularly good viscosity regulating effects. As materials with particularly good viscosity regulating effects, for example, water-soluble polymers can be used. In addition, as water-soluble polymers with particularly good viscosity regulating effects, the above-mentioned polysaccharides can be used, for example, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, and regenerated cellulose, or starch can be used.

[0217] Note that cellulose derivatives such as carboxymethyl cellulose, for example, can be easily used as viscosity modifiers by being converted into salts such as sodium salts or ammonium salts of carboxymethyl cellulose to improve their solubility. Due to the increased solubility, the dispersibility of active materials or other components can be improved when forming a slurry for an electrode. In this specification, etc., cellulose and cellulose derivatives used as binders for electrodes include their salts.

[0218] By dissolving a water-soluble polymer in water to stabilize its viscosity, the active material and other materials used as a binder combination, such as styrene-butadiene rubber, can be stably dispersed in an aqueous solution. Since the water-soluble polymer has functional groups, it is expected to be easily and stably attached to the surface of the active material. Most cellulose derivatives such as carboxymethyl cellulose have functional groups such as hydroxyl groups or carboxyl groups. Since they have functional groups, the polymers are expected to interact with each other and widely cover the surface of the active material.

[0219] When the binder covering or contacting the surface of the active material forms a film, it is also expected to be used as a passivation film to exert an effect of inhibiting the decomposition of the electrolyte. Here, the "passivation film" is a film that has no conductivity or very low conductivity. For example, when the passivation film is formed on the surface of the active material, it can inhibit the decomposition of the electrolyte at the battery reaction potential. More preferably, the passivation film can transmit lithium ions while inhibiting conductivity.

[0220] <Conductive Materials> Conductive materials are also called conductive agents or conductive aids, and carbon materials are used. By attaching conductive materials between multiple active materials, multiple active materials are electrically connected to each other and the conductivity is improved. Note that "attachment" not only refers to the physical close contact between the active material and the conductive material, but also refers to the concept that includes the following situations: when covalent bonds occur; when bonded by van der Waals forces; when the conductive material covers part of the surface of the active material; when the conductive material is embedded in the surface unevenness of the active material; when they are electrically connected without contact, etc.

[0221] The active material layer such as the positive electrode active material layer and the negative electrode active material layer preferably contains a conductive material.

[0222] As the conductive material, for example, any one or two or more of carbon black such as acetylene black and furnace black, graphite such as artificial graphite and natural graphite, carbon fibers such as carbon nanofibers and carbon nanotubes, and graphene compounds can be used.

[0223] As the carbon fiber, for example, mesophase pitch carbon fiber, isotropic pitch carbon fiber, etc. can be used. In addition, as the carbon fiber, carbon nanofiber or carbon nanotube can be used. For example, carbon nanotube can be produced by vapor phase growth or the like.

[0224] The graphene compounds in this specification and the like include graphene, multilayer graphene, multigraphene, graphene oxide, multilayer graphene oxide, multigraphene oxide, reduced graphene oxide, reduced multilayer graphene oxide, reduced multigraphene oxide, graphene quantum dots, etc. Graphene compounds refer to compounds containing carbon and having a flat plate, sheet, etc. shape and having a two-dimensional structure formed by a six-membered ring composed of carbon atoms. The two-dimensional structure formed by the six-membered ring composed of carbon atoms can also be called a carbon sheet. Graphene compounds can also have functional groups. In addition, the graphene compound preferably has a curved shape. In addition, the graphene compound can also be curled up like a carbon nanofiber.

[0225] The content of the conductive material in the total amount of the active material layer is preferably 1 wt % to 10 wt %, more preferably 1 wt % to 5 wt %.

[0226] Unlike granular conductive materials such as carbon black that form point contact with the active material, the graphene compound can form a surface contact with low contact resistance, so the conductivity of the granular active material and the graphene compound can be improved with a smaller amount than that of a general conductive material. Therefore, the proportion of the active material in the active material layer can be increased. As a result, the discharge capacity of the battery can be increased.

[0227] Carbon compounds in the form of particles such as carbon black and graphite or fibrous carbon compounds such as carbon nanotubes can easily enter microspaces. Microspaces refer to, for example, regions between multiple active materials. By combining carbon compounds that can easily enter microspaces and sheet-like carbon compounds such as graphene that can impart conductivity to multiple particles, the density of the electrode can be increased and a good conductive path can be formed. The battery obtained by the manufacturing method of one embodiment of the present invention can have high capacity density and stability, so it is very effective as a vehicle-mounted battery.

[0228] <Positive Electrode Current Collector> As the positive electrode current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the positive electrode current collector, foil, plate, sheet, mesh, punched metal mesh, drawn metal mesh and the like can be appropriately used. The thickness of the positive electrode current collector is preferably 5 μm or more and 30 μm or less.

[0229] [negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. In addition, the negative electrode active material layer contains a negative electrode active material and may further include a conductive auxiliary agent and a binder.

[0230] <Negative Electrode Active Material> As the negative electrode active material, for example, an alloy material or a carbon material can be used.

[0231] As the negative electrode active material, an element that can perform a charge and discharge reaction by alloying / de-alloying reaction with lithium can be used. For example, a material containing at least one selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The capacity of such an element is higher than that of carbon, and in particular, the theoretical capacity of silicon is high, which is 4200mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Here, an element capable of performing a charge-discharge reaction through an alloying / de-alloying reaction with lithium, a compound containing the element, and the like are sometimes referred to as an alloy-based material.

[0232] In this specification, "SiO" refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO x Here, x preferably represents a value of 1 or a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0233] As the carbon material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon fiber (carbon nanotube), graphene, carbon black, or the like can be used.

[0234] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0235] When lithium ions are intercalated in graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li / Li + ). As a result, lithium-ion batteries using graphite can show high operating voltages. Graphite also has the following advantages: large capacity per unit volume; relatively small volume expansion; relatively cheap; and higher safety than lithium metal, so it is preferred.

[0236] In addition, as the negative electrode active material, oxides such as titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten dioxide (WO2), molybdenum dioxide (MoO2), etc.

[0237] In addition, as the negative electrode active material, Li 3N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N3 shows a large charge and discharge capacity (900 mAh / g, 1890 mAh / cm 3 ), so it is preferred.

[0238] When a nitride containing lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, so it can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, and is therefore preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0239] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorides such as FeF3, BiF3.

[0240] In addition, as another form of the negative electrode, it can also be a negative electrode that does not contain a negative electrode active material at the end of battery manufacturing. As a negative electrode that does not contain a negative electrode active material, for example, the following negative electrode can be used, which only contains a negative electrode collector at the end of forming the battery manufacturing, and the lithium ions separated from the positive electrode active material due to the charging of the battery are precipitated in the form of lithium metal on the negative electrode collector, thereby forming a negative electrode active material layer. The battery using this negative electrode is sometimes called a negative electrode-free (anode-free) battery, etc.

[0241] When using a negative electrode that does not contain a negative electrode active material, a film for homogenizing the precipitation of lithium may also be included on the negative electrode current collector. As a film for homogenizing the precipitation of lithium, for example, a solid electrolyte with lithium ion conductivity can be used. As a solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, and a polymer solid electrolyte can be used. Among them, the film of the polymer solid electrolyte is relatively easy to form evenly on the negative electrode current collector, so it is suitable for a film for homogenizing the precipitation of lithium. In addition, as a film for homogenizing the precipitation of lithium, for example, a metal film that forms an alloy with lithium can be used. As a metal film that forms an alloy with lithium, for example, a magnesium metal film can be used. Since lithium and magnesium form a solid solution in a wider composition range, it is suitable for a film for uniformly precipitating lithium.

[0242] In addition, when using a negative electrode that does not contain a negative electrode active material, a negative electrode current collector having concave and convex portions can be used. When using a negative electrode current collector having concave and convex portions, the concave portions of the negative electrode current collector are cavities that are easy to precipitate lithium contained in the negative electrode current collector, thereby preventing the shape of lithium from becoming dendritic when it precipitates.

[0243] As the conductive material and the binder which may be contained in the negative electrode active material layer, the same conductive material and the binder which may be contained in the positive electrode active material layer may be used.

[0244] <Negative Electrode Current Collector> As the negative electrode current collector, copper or the like may be used in addition to the same materials as the positive electrode current collector. In addition, as the negative electrode current collector, it is preferable to use a material that does not alloy with carrier ions such as lithium.

[0245] [Electrolyte] The electrolyte comprises a solvent and an electrolyte. As the solvent of the electrolyte, an aprotic organic solvent is preferably used, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme (methyl diglyme), acetonitrile, benzonitrile, tetrahydrofuran, cyclopentane sulfone, one of sultones, or two or more of the above can be used in any combination and ratio.

[0246] In addition, by using one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility as the solvent of the electrolyte, even if the internal temperature rises due to the internal short circuit or overcharge of the secondary battery, the rupture and / or ignition of the secondary battery can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As the organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as the anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0247] In addition, as the electrolyte dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO 2) One of the lithium salts such as (CF3SO2), LiN(C2F5SO2)2, etc., or two or more of the above can be used in any combination and proportion.

[0248] As the electrolyte for the secondary battery, it is preferred to use a highly purified electrolyte with a low content of granular dust or elements other than the constituent elements of the electrolyte (hereinafter referred to as "impurities"). Specifically, the proportion of impurities in the weight of the electrolyte is preferably less than 1%, more preferably less than 0.1%, and further preferably less than 0.01%.

[0249] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or dinitrile compounds such as succinonitrile and adiponitrile, fluorobenzene, ethylene glycol bis(propionitrile) ether, etc. may also be added to the electrolyte. The concentration of the added material can be set to, for example, more than 0.1wt% and less than 5wt% in the solvent as a whole. VC or LiBOB are easy to form a good covering portion, so they are particularly preferred. Note that additives sometimes become a film attached to the surface of the active material during the aging treatment of the secondary battery. Therefore, in a secondary battery that has been charged to a certain extent, at least a portion of the additives are sometimes not detected from the electrolyte.

[0250] Alternatively, a polymer gel electrolyte in which a polymer is swollen with an electrolyte solution may be used.

[0251] Furthermore, by using a polymer gel electrolyte, safety against leakage etc. is improved, and the secondary battery can be made thinner and lighter.

[0252] As the gelled polymer, silicone gel, acrylic acid gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, fluorine polymer gel, etc. can be used.

[0253] As the polymer, for example, a polymer having a polyoxyalkylene structure such as polyethylene oxide (PEO), PVDF and polyacrylonitrile, and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. In addition, the formed polymer can also have a porous shape.

[0254] In addition, solid electrolytes containing inorganic materials such as sulfides or oxides, solid electrolytes containing polymer materials such as PEO (polyethylene oxide), etc. can be used instead of electrolytes. When a solid electrolyte is used, it is not necessary to set a separator and / or a spacer. In addition, since the entire battery can be solidified, there is no worry about leakage and safety is significantly improved.

[0255] [Isolated Body] When the electrolyte includes an electrolyte solution, a separator is disposed between the positive electrode and the negative electrode. As the separator, for example, the following materials can be used: a material formed of a fiber having cellulose such as paper, a nonwoven fabric, a glass fiber, a ceramic, or a synthetic fiber such as nylon (polyamide), vinylon (polyvinyl alcohol-based fiber), polyester, acrylic resin, polyolefin, or polyurethane. The separator is preferably processed into a bag shape and disposed so as to surround either the positive electrode or the negative electrode.

[0256] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0257] By coating ceramic materials, the oxidation resistance is improved, thereby suppressing the degradation of the separator during high-voltage charging and discharging, thereby improving the reliability of the secondary battery. By coating fluorine materials, it is easy to make the separator close to the electrode, which can improve the output characteristics. By coating polyamide materials, especially aromatic polyamide, the heat resistance can be improved, thereby improving the safety of the secondary battery.

[0258] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0259] By adopting a separator with a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the capacity per unit volume of the secondary battery can be increased.

[0260] [Outer packaging] As the outer packaging body included in the secondary battery, for example, a metal material such as aluminum or a resin material can be used. In addition, a film-shaped outer packaging body can also be used. As the film, for example, a three-layer structure film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is provided on a film composed of a material such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as a polyamide resin and a polyester resin is provided on the metal film as the outer surface of the outer packaging body.

[0261] (Implementation 4) In this embodiment, various examples of shapes of secondary batteries including a positive electrode manufactured by the manufacturing method described in the above embodiment will be described.

[0262] [Coin-type secondary battery] An example of a coin-type secondary battery will be described. Fig.11A This is an exploded perspective view of a coin-type (single-layer flat) secondary battery. Fig. 11B This is its appearance picture. Fig. 11C Coin-type secondary batteries are mainly used in small electronic devices.

[0263] In order to easily understand the overlapping relationship (upper and lower relationship and position relationship) of components, Fig.11A A schematic diagram is used. Therefore, Fig.11A Not with Fig. 11B Exactly the same picture.

[0264] exist Fig.11A In the embodiment, the positive electrode 304, the separator 310, the negative electrode 307, the spacer 322, and the gasket 312 are stacked. Then, the negative electrode can 302, the positive electrode can 301, and the gasket are used to seal the above components. Fig.11A The gasket used for sealing is not shown. The spacer 322 and the gasket 312 are used to protect the inside or fix the position in the tank when the positive electrode tank 301 and the negative electrode tank 302 are pressed together. The spacer 322 and the gasket 312 are made of stainless steel or insulating material.

[0265] A stacked structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is referred to as a positive electrode 304 .

[0266] Fig. 11B It is a perspective view of the manufactured coin-type secondary battery.

[0267] In the coin-type secondary battery 300, a positive electrode can 301 serving as a positive terminal and a negative electrode can 302 serving as a negative terminal are insulated and sealed by a gasket 303 formed of polypropylene or the like. A positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. A negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector 308. The negative electrode 307 is not limited to a laminated structure, and a lithium metal foil or an alloy foil of lithium and aluminum may be used.

[0268] In the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 , the active material layer may be formed on one surface of the positive electrode and the negative electrode, respectively.

[0269] As the positive electrode can 301 and the negative electrode can 302, metals such as nickel, aluminum, and titanium, alloys thereof, and alloys of these and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, etc., the positive electrode can 301 and the negative electrode can 302 are preferably covered with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0270] By immersing the negative electrode 307, the positive electrode 304 and the separator 310 in an electrolyte, Fig. 11C As shown, the positive electrode can 301 is placed at the bottom, the positive electrode 304, the separator 310, the negative electrode 307 and the negative electrode can 302 are stacked in order, and the positive electrode can 301 and the negative electrode can 302 are pressed with the gasket 303 interposed therebetween to manufacture the coin-type secondary battery 300.

[0271] By adopting the above structure, it is possible to manufacture the coin-type secondary battery 300 having a high discharge capacity and excellent cycle characteristics.

[0272] [Cylindrical secondary battery] Next, refer to Fig. 12A An example of a cylindrical secondary battery will be described. Fig. 12A As shown, the top surface of the cylindrical secondary battery 616 includes a positive electrode cover (battery cover) 601, and the side and bottom surfaces thereof include a battery can (outer can) 602. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0273] Fig. 12B It is a diagram schematically showing a cross section of a cylindrical secondary battery. Fig. 12B The cylindrical secondary battery shown includes a positive electrode cover (battery cover) 601 on the top surface and a battery can (outer can) 602 on the side and bottom surfaces. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0274] A battery element is provided inside the hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are wound around a separator 605. Although not shown, the battery element is wound around the central axis. One end of the battery can 602 is closed and the other end is open. As the battery can 602, metals such as nickel, aluminum, titanium, their alloys, and alloys of them and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, the battery can 602 is preferably covered with nickel, aluminum, etc. On the inside of the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched by a pair of opposing insulating plates 608 and insulating plates 609. In addition, a non-aqueous electrolyte (not shown) is injected into the interior of the battery can 602 in which the battery element is provided. As a non-aqueous electrolyte, the same electrolyte as a coin-type secondary battery can be used.

[0275] Since the positive electrode and the negative electrode used for the cylindrical storage battery are wound, the active material is preferably formed on both surfaces of the current collector.

[0276] By using the positive electrode active material 100 obtained in Embodiments 1 and 2, etc., for the positive electrode 604, a cylindrical secondary battery 616 having a high capacity, a high discharge capacity, and excellent cycle characteristics can be manufactured.

[0277] The positive electrode 604 is connected to the positive terminal (positive electrode current collecting wire) 603, and the negative electrode 606 is connected to the negative terminal (negative electrode current collecting wire) 607. Metal materials such as aluminum can be used for both the positive terminal 603 and the negative terminal 607. The positive terminal 603 is resistance-welded to the safety valve mechanism 613, and the negative terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cover 601 through a PTC (Positive Temperature Coefficient) element 611. When the internal pressure of the battery rises to exceed a specified threshold, the safety valve mechanism 613 cuts off the electrical connection between the positive electrode cover 601 and the positive electrode 604. In addition, the PTC element 611 is a thermally sensitive resistance element whose resistance increases when the temperature rises, and limits the current by increasing the resistance to prevent abnormal heating. As a PTC element, barium titanate (BaTiO3)-based semiconductor ceramics, etc. can be used.

[0278] Fig. 12C An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616. The positive electrode of each secondary battery contacts a conductor 624 separated by an insulator 625, and the positive electrodes are electrically connected to each other. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, the negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge and discharge control circuit for performing charge and discharge or a protection circuit for preventing overcharge and / or overdischarge can be used.

[0279] Fig.12D An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 through a wiring 627. The plurality of secondary batteries 616 may be connected in parallel or in series, or may be connected in parallel and then in series. By configuring the power storage system 615 including the plurality of secondary batteries 616, a large amount of electric power can be obtained.

[0280] A plurality of secondary batteries 616 may be connected in parallel and then connected in series.

[0281] In addition, a temperature control device may be included between the plurality of secondary batteries 616. When the secondary battery 616 is overheated, it can be cooled by the temperature control device, and when the secondary battery 616 is overcooled, it can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is not easily affected by the external temperature.

[0282] In addition, Fig.12D In FIG. 6 , the power storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the plurality of secondary batteries 616 via the conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the plurality of secondary batteries 616 via the conductive plate 614.

[0283] [Other structural examples of secondary batteries] An example of the structure of a secondary battery will be described using FIG. 13 and FIG. 14 .

[0284] Fig.13A The secondary battery 913 shown includes a winding body 950 provided with a terminal 951 and a terminal 952 inside a frame 930. The winding body 950 is impregnated with an electrolyte inside the frame 930. The terminal 952 is in contact with the frame 930, and the terminal 951 is not in contact with the frame 930 due to an insulating material or the like. Note that for convenience, although Fig.13A Frame 930 is shown separately in the figure, but in reality, winding body 950 is covered by frame 930, and terminals 951 and 952 extend outside frame 930. Frame 930 can be made of a metal material (such as aluminum) or a resin material.

[0285] In addition, if Fig. 13B As shown, multiple materials can also be used to form Fig.13A For example, in the frame 930 shown in FIG. Fig. 13B In the secondary battery 913 shown, a frame body 930 a and a frame body 930 b are bonded together, and a wound body 950 is provided in a region surrounded by the frame bodies 930 a and 930 b.

[0286] As the frame 930a, an insulating material such as an organic resin can be used. In particular, by using a material such as an organic resin to form the surface of the antenna, it is possible to suppress the shielding of the electric field by the secondary battery 913. In addition, if the electric field shielding caused by the frame 930a is small, the antenna can also be provided inside the frame 930a. As the frame 930b, for example, a metal material can be used.

[0287] Furthermore, Fig. 13C The structure of the wound body 950 is shown. The wound body 950 includes a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is formed by overlapping the negative electrode 931 and the positive electrode 932 with the separator 933 interposed therebetween to form a laminated sheet, and then winding the laminated sheet. In addition, a plurality of layers of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked.

[0288] Alternatively, a secondary battery 913 including a wound body 950 a as shown in FIG. 14 may be used. Fig.14A The wound body 950a shown includes a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 includes a negative electrode active material layer 931a. The positive electrode 932 includes a positive electrode active material layer 932a.

[0289] By using the positive electrode active material 100 that can be obtained in Embodiments 1 and 2, etc., for the positive electrode 932, the secondary battery 913 having a high capacity, a high discharge capacity, and excellent cycle characteristics can be manufactured.

[0290] The separator 933 is wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, the width of the negative electrode active material layer 931a is preferably wider than the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is preferred because of its good safety and productivity.

[0291] like Fig. 14B As shown, the negative electrode 931 is electrically connected to the terminal 951 by ultrasonic bonding, welding or pressing. The terminal 951 is electrically connected to the terminal 911a. In addition, the positive electrode 932 is electrically connected to the terminal 952 by ultrasonic bonding, welding or pressing. The terminal 952 is electrically connected to the terminal 911b.

[0292] like Fig. 14C As shown, the wound body 950a and the electrolyte are covered by the frame 930 to form a secondary battery 913. The frame 930 is preferably provided with a safety valve, an overcurrent protection element, etc. The safety valve is a valve that is opened at a specified internal pressure in the frame 930 to prevent battery rupture.

[0293] like Fig. 14B As shown, the secondary battery 913 may also include a plurality of winding bodies 950a. By using a plurality of winding bodies 950a, a secondary battery 913 with a larger discharge capacity can be realized. Fig.14A and Fig. 14B The other components of the secondary battery 913 shown can be referred to FIG. 13A to FIG. 13C Description of the secondary battery 913 shown.

[0294] <Laminated secondary battery> then, Fig.15A and Fig. 15B 1 is an external view showing an example of a laminated secondary battery. Fig.15A and Fig. 15B A positive electrode 503 , a negative electrode 506 , a separator 507 , an outer package 509 , a positive electrode lead electrode 510 , and a negative electrode lead electrode 511 are all shown.

[0295] Fig.16A The appearance diagram of the positive electrode 503 and the negative electrode 506 is shown. The positive electrode 503 includes a positive electrode collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode collector 501. In addition, the positive electrode 503 has an area where the positive electrode collector 501 is partially exposed (hereinafter referred to as the tab area). The negative electrode 506 includes a negative electrode collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode collector 504. In addition, the negative electrode 506 has an area where the negative electrode collector 504 is partially exposed, namely, the tab area. The area or shape of the tab area of ​​the positive electrode and the negative electrode is not limited to Fig.16A Example shown.

[0296] <Method for manufacturing laminated secondary battery> Here, refer to Fig. 16B and Fig. 16C Yes Fig.15A An example of a method for producing a laminated secondary battery whose appearance is shown in FIG. 1 is described below.

[0297] First, the negative electrode 506, the separator 507, and the positive electrode 503 are stacked. Fig. 16B The stacked negative electrode 506, separator 507 and positive electrode 503 are shown. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. In addition, it can also be said that it is a stacked body composed of negative electrodes, separators, and positive electrodes. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. As the joining, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0298] Next, the negative electrode 506 , the separator 507 , and the positive electrode 503 are arranged on the outer packaging body 509 .

[0299] Below, as Fig. 16C As shown, the outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of the outer package 509 is joined. As the joining method, for example, heat pressing or the like can be used. At this time, in order to inject the electrolyte later, a non-joined area (hereinafter referred to as the introduction port) is provided on a part (or one side) of the outer package 509.

[0300] Next, the electrolyte is introduced into the inner side of the outer packaging body 509 from the introduction port provided in the outer packaging body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert gas atmosphere. Finally, the introduction port is joined. In this way, the laminated secondary battery 500 can be manufactured.

[0301] By using the positive electrode active material 100 that can be obtained in Embodiments 1 and 2, etc., for the positive electrode 503, a secondary battery 500 having a high capacity, a high discharge capacity, and excellent cycle characteristics can be manufactured.

[0302] (Implementation method 5) In this embodiment, an example of a vehicle equipped with a secondary battery according to one embodiment of the present invention is described.

[0303] As a vehicle, a secondary battery can typically be used in a car. As a car, a new generation of clean energy vehicles such as a hybrid electric vehicle (HV), an electric vehicle (EV) or a plug-in hybrid electric vehicle (also referred to as PHEV or PHV) can be cited, and a secondary battery can be used as one of the power sources installed in the car. Vehicles are not limited to cars. For example, as a vehicle, a tram, a monorail, a ship, a submarine (submersible, unmanned submarine), a flying object (helicopter, unmanned aircraft (drone), airplane, rocket, satellite), an electric bicycle, an electric motorcycle, etc. can be cited, and a secondary battery including one embodiment of the present invention can be applied to these vehicles.

[0304] Fig. 17C This is an example of using the secondary battery of the present invention in an electric vehicle (EV). In an electric vehicle, a first battery 1301a, 1301b as a secondary battery for main drive and a second battery 1311 for supplying power to an inverter 1312 for starting an engine 1304 are provided. The second battery 1311 is also called a cranking battery (also called a starting battery). The second battery 1311 only needs to have a high output and does not need to have a high capacity. In addition, the capacity of the second battery 1311 is smaller than that of the first battery 1301a, 1301b.

[0305] The internal structure of the first battery 1301a can be either Fig. 13C or Fig.14A The winding type shown can also be used Fig.15A or Fig. 15B The stacked type shown. In addition, the first battery 1301a may also use the all-solid battery of Embodiment 6. By using the all-solid battery of Embodiment 6 as the first battery 1301a, a high capacity can be achieved, safety is improved, and miniaturization and weight reduction can be achieved.

[0306] In this embodiment, an example of connecting the first battery 1301a and 1301b in parallel is shown, but more than three batteries may be connected in parallel. In addition, as long as sufficient power can be stored in the first battery 1301a, the first battery 1301b may not be provided. By forming a battery pack with multiple secondary batteries, a larger amount of power can be taken out. Multiple secondary batteries may be connected in parallel, in series, or in series after being connected in parallel. Sometimes multiple secondary batteries are referred to as battery packs.

[0307] In order to cut off the power from the plurality of secondary batteries, the vehicle-mounted secondary battery includes a charging plug or a circuit breaker that can cut off the high voltage without using a tool, which is provided in the first battery 1301a.

[0308] In addition, the power of the first battery 1301a, 1301b is mainly used to rotate the engine 1304, and the power is also supplied to the 42V series vehicle-mounted components (electric power steering system 1307, heater 1308, defogger 1309, etc.) through the DCDC circuit 1306. In the case where the rear wheel includes a rear engine 1317, the first battery 1301a is used to rotate the rear engine 1317.

[0309] Furthermore, the second battery 1311 supplies power to 14V series vehicle-mounted components (audio 1313 , power windows 1314 , lights 1315 , etc.) via the DCDC circuit 1310 .

[0310] Next, use Fig.17A The first battery 1301a is described.

[0311] Fig.17A An example of using nine rectangular secondary batteries 1300 as a battery pack 1415 is shown. In addition, the nine rectangular secondary batteries 1300 are connected in series and one electrode is fixed using a fixing portion 1413 formed of an insulator and the other electrode is fixed using a fixing portion 1414 formed of an insulator. In this embodiment, an example of fixing using fixing portions 1413 and 1414 is shown, but it can also be stored in a battery storage box (also referred to as a frame). Assuming that the vehicle is vibrated or shaken from the outside (road surface, etc.), it is preferable to fix multiple secondary batteries using fixing portions 1413, 1414, a battery storage box, etc. In addition, one electrode is electrically connected to the control circuit unit 1320 via wiring 1421. In addition, the other electrode is electrically connected to the control circuit unit 1320 via wiring 1422.

[0312] Alternatively, a memory circuit including a transistor using an oxide semiconductor may be used as the control circuit portion 1320. A charge control circuit or a battery control system including a memory circuit including a transistor using an oxide semiconductor is sometimes referred to as a BTOS (Battery operating system or Battery oxide semiconductor).

[0313] It is preferred to use a metal oxide used as an oxide semiconductor. For example, as the metal oxide, it is preferred to use In-M2-Zn oxide (the element M2 is one or more selected from aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten and magnesium). In particular, the In-M-Zn oxide that can be applied to the metal oxide is preferably CAAC-OS (C-Axis Aligned Crystal Oxide Semiconductor). Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). In addition, In-Ga oxide and In-Zn oxide can also be used as metal oxides. CAAC-OS is an oxide semiconductor including multiple crystalline regions, and the c-axes of the multiple crystalline regions are oriented in a specific direction. In addition, the specific direction refers to the thickness direction of the CAAC-OS film, the normal direction of the formed surface of the CAAC-OS film, or the normal direction of the surface of the CAAC-OS film. In addition, the crystalline region is a region with periodic atomic arrangement. Note that when the atomic arrangement is regarded as a lattice arrangement, the crystalline region is also a region with a consistent lattice arrangement.

[0314] In addition, "CAC-OS" refers to a structure in which the material is separated into a first region and a second region to form a mosaic shape, and the first region is distributed in the film (hereinafter also referred to as a cloud shape). That is, CAC-OS refers to a composite metal oxide having a structure in which the first region and the second region are mixed. Note that it is sometimes difficult to observe a clear boundary between the first region and the second region.

[0315] For example, in the CAC-OS of In-Ga-Zn oxide, based on the EDX mapping image obtained by energy dispersive X-ray spectroscopy (EDX), it can be confirmed that the structure has a region with In as the main component (first region) and a region with Ga as the main component (second region) that are unevenly distributed and mixed.

[0316] When CAC-OS is used for transistors, the complementary effect of the conductivity of the first region and the insulation of the second region can give CAC-OS a switch function (a function of controlling on / off). In other words, a portion of the CAC-OS material has a conductive function and another portion has an insulating function, and the entire material has a semiconductor function. By separating the conductive function and the insulating function, each function can be maximized. Therefore, by using CAC-OS for transistors, a high on-state current (I on ), high field effect mobility (μ) and good switching performance.

[0317] Oxide semiconductors have various structures and various characteristics. The oxide semiconductor of one embodiment of the present invention may include two or more of an amorphous oxide semiconductor, a polycrystalline oxide semiconductor, a-like OS, CAC-OS, nc-OS, and CAAC-OS.

[0318] In addition, the control circuit unit 1320 preferably uses a transistor containing an oxide semiconductor because the transistor can be used in a high temperature environment. In order to simplify the process, the control circuit unit 1320 can also be formed using a unipolar transistor. The operating ambient temperature range of the transistor containing an oxide semiconductor in the semiconductor layer is larger than that of the single-crystalline Si transistor, that is, above -40°C and below 150°C, and the characteristic change of the secondary battery when overheated is smaller than that of the single-crystalline Si transistor. The off-state current of the transistor containing an oxide semiconductor is also below the lower limit of the measurement at 150°C and does not depend on the temperature, but the temperature dependence of the off-state current characteristics of the single-crystalline Si transistor is large. For example, at 150°C, the off-state current of the single-crystalline Si transistor increases, and the switching ratio of the current does not become sufficiently large. The control circuit unit 1320 can improve safety. In addition, by combining with a secondary battery in which the positive electrode active material 100 that can be obtained in embodiments 1, 2, etc. is used for the positive electrode, a synergistic effect of safety can be obtained. The secondary battery and the control circuit unit 1320 using the positive electrode active material 100 obtained in the first and second embodiments, etc., for the positive electrode greatly contribute to reducing accidents such as fires caused by the secondary battery.

[0319] The control circuit unit 1320 using a storage circuit including a transistor using an oxide semiconductor can also be used as an automatic control device for a secondary battery for the causes of instability caused by ten conditions such as micro short circuits. As functions for solving the causes of instability of secondary batteries, there can be cited prevention of overcharging, prevention of overcurrent, control of overheating during charging, cell balancing in a battery pack, prevention of overdischarge, a capacity meter, automatic control of charging voltage and current according to temperature, control of charging current according to the degree of degradation, detection of abnormal behavior of micro short circuits, prediction of abnormalities regarding micro short circuits, etc. The control circuit unit 1320 has at least one of the above functions. In addition, ultra-miniaturization of the automatic control device for secondary batteries can be achieved.

[0320] In addition, "micro short circuit" refers to a very small short circuit inside the secondary battery. It is not a state where the positive and negative electrodes of the secondary battery cannot be charged or discharged due to a short circuit, but a phenomenon in which a short circuit current flows slightly in a very small short circuit portion. Since a large voltage change occurs even in a short and very small portion, this abnormal voltage value will affect subsequent speculation.

[0321] One of the reasons for micro short circuits is believed to be that due to repeated charging and discharging, uneven distribution of positive electrode active materials occurs, local current concentration occurs in part of the positive electrode and part of the negative electrode, and part of the separator becomes inoperative, or side reactions produce side reactants, leading to micro short circuits.

[0322] In addition to micro short circuits, the control circuit unit 1320 detects the terminal voltage of the secondary battery and manages the charge and discharge state of the secondary battery. For example, to prevent overcharging, both the output transistor of the charging circuit and the blocking switch can be turned off at almost the same time.

[0323] then, Fig. 17B Show Fig.17A An example of a block diagram of a battery pack 1415 is shown.

[0324] The control circuit unit 1320 includes: a switch unit 1324 including at least a switch for preventing overcharging and a switch for preventing overdischarging; a control circuit 1322 for controlling the switch unit 1324; and a voltage measuring unit of the first battery 1301a. In the control circuit unit 1320, the upper limit voltage and the lower limit voltage of the secondary battery used are set to control the upper limit of the current flowing from the outside or the upper limit of the output current flowing to the outside. The range above the lower limit voltage and below the upper limit voltage of the secondary battery is the recommended voltage range. When the voltage is outside this range, the switch unit 1324 functions and serves as a protection circuit. In addition, the control circuit unit 1320 controls the switch unit 1324 to prevent overdischarge and / or overcharge, so it can also be called a protection circuit. For example, when the control circuit 1322 detects a voltage that will become overcharge, the current is shielded by closing the switch of the switch unit 1324. In addition, the function of shielding the current according to the increase in temperature can also be set by setting a PTC element in the charge and discharge path. In addition, the control circuit unit 1320 includes an external terminal 1325 (+IN) and an external terminal 1326 (−IN).

[0325] The switch section 1324 can be formed by combining n-channel transistors or p-channel transistors. The switch section 1324 is not limited to a switch including a Si transistor using single crystal silicon. For example, the switch section 1324 can also be formed using power transistors such as Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenic), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaOx (gallium oxide; x is a real number greater than 0). In addition, the storage element using the OS transistor can be freely configured by stacking it on a circuit using the Si transistor, so it is easy to achieve integration. In addition, the OS transistor can be manufactured using the same manufacturing device as the Si transistor, so it can be manufactured at a low cost. That is, by stacking the control circuit section 1320 using the OS transistor on the switch section 1324 for integration, the switch section 1324 and the control circuit section 1320 can be integrated into one chip. The volume occupied by the control circuit unit 1320 can be reduced, so miniaturization can be achieved.

[0326] The first battery 1301a and 1301b mainly supply power to 42V series (high voltage series) vehicle-mounted equipment, while the second battery 1311 supplies power to 14V series (low voltage series) vehicle-mounted equipment. In many cases, the second battery 1311 adopts a lead-acid battery due to cost advantages. However, lead-acid batteries have the disadvantages of large self-discharge compared to lithium-ion batteries and easy deterioration due to a phenomenon called sulfation. When a lithium-ion battery is used as the second battery 1311, there is an advantage of no maintenance. In particular, in order to prevent the situation that the engine cannot be started even if the first batteries 1301a and 1301b have residual capacity when the second battery 1311 of the starting inverter fails to work, when the second battery 1311 is a lead-acid battery, power is supplied from the first battery to the second battery to charge in a manner that always maintains a fully charged state.

[0327] This embodiment shows an example in which lithium ion batteries are used in both the first battery 1301a and the second battery 1311. A lead acid battery, a solid-state battery, or a double-layer capacitor may also be used for the second battery 1311. For example, a solid-state battery of embodiment 6 may also be used. By using the solid-state battery of embodiment 6 as the second battery 1311, a high capacity can be achieved, thereby achieving miniaturization and lightness.

[0328] In addition, the regenerative energy caused by the rotation of the tire 1316 is transmitted to the engine 1304 through the transmission 1305, and is charged to the second battery 1311 from the engine controller 1303 and the battery controller 1302 through the control circuit unit 1321. In addition, the first battery 1301a is charged from the battery controller 1302 through the control circuit unit 1320. In addition, the first battery 1301b is charged from the battery controller 1302 through the control circuit unit 1320. In order to efficiently charge the regenerative energy, it is preferable that the first batteries 1301a and 1301b can be charged at a high speed.

[0329] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b, etc. The battery controller 1302 sets the charging conditions according to the charging characteristics of the secondary battery to be used and performs high-speed charging.

[0330] In addition, although not shown in the figure, when connected to an external charger, the charger socket or the charger connection cable is electrically connected to the battery controller 1302. The power supplied from the external charger is charged to the first battery 1301a, 1301b through the battery controller 1302. In addition, some chargers are provided with a control circuit without using the function of the battery controller 1302, but in order to prevent overcharging, it is preferred to charge the first battery 1301a, 1301b through the control circuit unit 1320. In addition, sometimes the connection cable or the charger connection cable is provided with a control circuit. The control circuit unit 1320 is sometimes referred to as an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) provided in the electric vehicle. CAN is one of the serial communication standards used as an in-vehicle LAN. In addition, the ECU includes a microcomputer. In addition, the ECU uses a CPU or a GPU.

[0331] As an external charger installed in a charging station, there are 100V outlet-200V outlet or three-phase 200V and 50kW outlet, etc. In addition, it is also possible to charge by supplying power from an external charging device through a contactless power supply method.

[0332] In order to charge the battery in a short time during high-speed charging, a secondary battery that can withstand charging at a high voltage is desired.

[0333] In addition, when graphene is used as a conductive additive and the capacity can be suppressed from decreasing and maintained at a high capacity even if the thickness of the electrode layer is increased and the load is increased, a synergistic effect can be achieved to realize a secondary battery with greatly improved electrical characteristics. In particular, it is very effective for secondary batteries used in vehicles, and a longer driving distance can be achieved without increasing the weight ratio of the secondary battery relative to the total weight of the vehicle, specifically, a vehicle that can travel a distance of more than 500 km per charge.

[0334] In particular, the secondary battery of the present embodiment described above can increase the operating voltage of the secondary battery by using the positive electrode active material 100 described in Embodiments 1 and 2, thereby increasing the available capacity as the charging voltage increases. In addition, by using the positive electrode active material 100 described in Embodiments 1 and 2 for the positive electrode, a secondary battery for a vehicle with good cycle characteristics can be provided.

[0335] Next, an example in which a secondary battery as one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.

[0336] In addition, when Fig.12D , Fig. 14C , Fig.17A When any of the secondary batteries shown in is installed in a vehicle, a new generation of clean energy vehicles such as hybrid electric vehicles (HV), electric vehicles (EV) or plug-in hybrid electric vehicles (PHV) can be realized. In addition, the secondary battery can also be installed in agricultural machinery, electric bicycles including electric-assisted bicycles, motorcycles, electric wheelchairs, electric karts, ships, submarines, airplanes, rockets, artificial satellites, space probes, planetary probes or spacecraft. The secondary battery of one embodiment of the present invention can be a high-capacity secondary battery. Therefore, the secondary battery of one embodiment of the present invention is suitable for miniaturization and lightweight, and can be suitable for use in transportation vehicles.

[0337] 18A to 18D A transport vehicle using one embodiment of the present invention is shown. Fig.18A The car 2001 shown is an electric car using an electric motor as a power source for running. Alternatively, the car 2001 is a hybrid car that can use an electric motor and an engine as a power source for running. When the secondary battery is installed in the vehicle, the example of the secondary battery shown in the embodiment 4 can be set in one or more parts. Fig.18A The illustrated automobile 2001 includes a battery pack 2200 including a secondary battery module in which a plurality of secondary batteries are connected, and preferably also includes a charge control device electrically connected to the secondary battery module.

[0338] In addition, in the automobile 2001, the secondary battery of the automobile 2001 can be charged by supplying power from an external charging device using a plug-in method or a contactless power supply method. When charging, the charging method or the specifications of the connector can be appropriately performed according to the methods specified by CHAdeMO (a registered trademark in Japan) or the combined charging system "Combined Charging System". As a charging device, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the power storage device installed in the automobile 2001 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an AC / DC converter.

[0339] In addition, although not shown in the figure, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between two vehicles. Furthermore, a solar cell can be set on the outside of the vehicle to charge the secondary battery when it is parked or driving. Such non-contact power supply can be achieved using electromagnetic induction or magnetic field resonance.

[0340] exist Fig.18B In the diagram, a large transport vehicle 2002 including an electrically controlled engine is shown as an example of a transport vehicle. The secondary battery module of the transport vehicle 2002 is, for example, a secondary battery module having a maximum voltage of 170V, in which four secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series and 48 cells are connected. The battery pack 2201 has the same characteristics as the battery pack 2201 except for the number of secondary batteries constituting the secondary battery module. Fig.18A The functions are the same, so the description is omitted.

[0341] exist Fig.18C In the figure, a large transport vehicle 2003 including an electrically controlled engine is shown as an example. The secondary battery module of the transport vehicle 2203 is, for example, a secondary battery module having a maximum voltage of 600V in which more than 100 secondary batteries having a nominal voltage of 3.0V or more and 5.0V or less are connected in series. Therefore, a secondary battery having less uneven characteristics is required. By using a secondary battery in which the positive electrode active material 100 described in embodiments 1 and 2, etc. is used for the positive electrode, a secondary battery having stable battery characteristics can be manufactured, and mass production can be performed at low cost from the perspective of yield. In addition, in addition to the difference in the number of secondary batteries constituting the secondary battery module, the battery pack 2202 has the same Fig. 20A The functions are the same, so the description is omitted.

[0342] exist Fig.18D , an aircraft 2004 equipped with an engine burning fuel is shown as an example. Fig.18D The aircraft 2004 shown includes wheels for taking off and landing, so it can be said that the aircraft 2004 is a type of transportation vehicle. In the aircraft 2004, multiple secondary batteries are connected to form a secondary battery module and include a battery pack 2203 having a secondary battery module and a charging control device.

[0343] The secondary battery module of the aircraft 2004 has, for example, eight 4V secondary batteries connected in series and a maximum voltage of 32V. In addition to the number of secondary batteries constituting the secondary battery module of the battery pack 2203, the Fig.18A The functions are the same, so the description is omitted.

[0344] Fig.18E As an example, an artificial satellite 2005 using a secondary battery 2204 is shown. Since the artificial satellite 2005 is used in the extremely low temperature space, it is preferable to include a secondary battery 2204 of one embodiment of the present invention having good low temperature resistance. In addition, the secondary battery 2204 is preferably installed inside the artificial satellite 2005 in a state covered with a heat-insulating member.

[0345] (Implementation method 6) In this embodiment, as an example of a vehicle equipped with a secondary battery, an example in which a lithium ion battery according to one embodiment of the present invention is mounted on a two-wheeled vehicle or a bicycle is described.

[0346] Fig.19A An example of an electric bicycle using the power storage device according to one embodiment of the present invention will be described. Fig.19A The electric bicycle 8700 shown can use the power storage device of one embodiment of the present invention. For example, the power storage device of one embodiment of the present invention includes a plurality of storage batteries and a protection circuit.

[0347] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 supplies power to a motor that assists the rider. In addition, the power storage device 8702 is portable. Fig.19B The power storage device 8702 taken out of the bicycle is shown. The power storage device 8702 has a plurality of storage batteries 8701 included in the power storage device of one embodiment of the present invention built in, and the remaining power, etc. can be displayed by the display unit 8703. In addition, the power storage device 8702 includes a control circuit 8704 shown in Embodiment 7 that can perform charging control or abnormality detection of the secondary battery. The control circuit 8704 is electrically connected to the positive electrode and the negative electrode of the storage battery 8701. In addition, by combining with a secondary battery using the positive electrode active material 100 that can be obtained in Embodiments 1, 2, etc. for the positive electrode, a synergistic effect of safety can be obtained. The secondary battery using the positive electrode active material 100 that can be obtained in Embodiments 1, 2, etc. for the positive electrode and the control circuit 8704 have made a great contribution to reducing accidents such as fires caused by secondary batteries.

[0348] Fig.19C This is an example of a two-wheeled vehicle using the power storage device of one embodiment of the present invention. Fig.19C The illustrated scooter 8600 includes a power storage device 8602, a side mirror 8601, and a turn signal lamp 8603. The power storage device 8602 can supply power to the turn signal lamp 8603. In addition, the power storage device 8602 equipped with a plurality of secondary batteries using the positive electrode active material 100 obtained in Embodiments 1 and 2 as a positive electrode can have a high capacity and contribute to miniaturization.

[0349] In addition, Fig.19C In the illustrated scooter 8600, the power storage device 8602 can be stored in the under-seat storage section 8604. Even if the under-seat storage section 8604 is small, the power storage device 8602 can be stored in the under-seat storage section 8604.

[0350] (Implementation 7) In this embodiment, an example of installing a secondary battery of one embodiment of the present invention in an electronic device is described. As an electronic device equipped with a secondary battery, for example, a television device (also referred to as a television or a television receiver), a display for a computer, a digital camera, a digital video camera, a digital photo frame, a mobile phone (also referred to as a mobile phone, a mobile phone device), a portable game console, a portable information terminal, a sound reproduction device, a large game console such as a pinball machine, etc. can be cited. As a portable information terminal, a notebook personal computer, a tablet terminal, an e-book terminal, a mobile phone, etc. can be cited.

[0351] Fig. 20A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, etc. in addition to a display unit 2102 mounted on a housing 2101. In addition, the mobile phone 2100 includes a secondary battery 2107. By including the secondary battery 2107 using the positive electrode active material 100 described in Embodiments 1 and 2 as a positive electrode, a high capacity can be achieved, and a structure that can cope with the space saving required for miniaturization of the housing can be achieved.

[0352] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, network communication, computer games, etc.

[0353] In addition to time setting, the operation button 2103 may have various functions such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0354] In addition, the mobile phone 2100 can perform short-range wireless communication standardized by the communication system. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0355] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0356] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a body sensor such as a temperature sensor, a touch sensor, a pressure sensor, or an acceleration sensor may be preferably installed as the sensor.

[0357] Fig. 20B An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 is also referred to as a drone. The unmanned aerial vehicle 2300 includes a secondary battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna. The secondary battery using the positive electrode active material 100 obtained in embodiments 1, 2, etc. for the positive electrode has a high energy density and high safety, so it can be used safely for a long period of time, so it is suitable as a secondary battery installed in the unmanned aerial vehicle 2300.

[0358] Fig. 20C An example of a robot is shown. Fig. 20C The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0359] The microphone 6402 has a function of detecting the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0360] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0361] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0362] The robot 6400 is provided with a secondary battery 6409 and a semiconductor device or an electronic component according to one embodiment of the present invention. The secondary battery using the positive electrode active material 100 obtained in the first and second embodiments, etc., for the positive electrode has high energy density and high safety, so it can be used safely for a long period of time, and is therefore suitable as the secondary battery 6409 installed in the robot 6400.

[0363] Fig.20D An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk by itself and can detect garbage 6310 and suck the garbage into the suction port set below.

[0364] The sweeping robot 6300 can determine whether there are obstacles such as walls, furniture, or steps by analyzing the image taken by the camera 6303. In addition, when an object such as a wire that may be entangled with the brush 6304 is found through image analysis, the rotation of the brush 6304 can be stopped. The internal area of ​​the sweeping robot 6300 is equipped with a secondary battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention. The secondary battery using the positive electrode active material 100 obtained in embodiments 1, 2, etc. for the positive electrode has high energy density and high safety, so it can be used safely for a long time for a long time, so it is suitable as a secondary battery 6306 installed in the sweeping robot 6300. [Example 1]

[0365] In this example, a positive electrode active material 100 having a large crystal grain size was manufactured and its characteristics were evaluated.

[0366] <Manufacturing of Positive Electrode Active Material> Reference Figure 6 as well as Figure 7 The manufacturing method shown illustrates the samples manufactured in this embodiment.

[0367] <Sample 1 to Sample 5> exist Figure 6 In step S11, nickel (II) sulfate is prepared as a nickel source, cobalt (II) sulfate is prepared as a cobalt source, and manganese (II) sulfate is prepared as a manganese source. In step S13, glycine is prepared as a chelating agent. These transition metal M sources are weighed so that they become 2 mol / L and Ni:Co:Mn=8:1:1 (atomic ratio), and glycine is weighed so that it becomes 0.200 mol / L, and pure water is added to it to dissolve it (step S14), thereby preparing an acid solution.

[0368] As the alkaline solution, a 5 mol / L sodium hydroxide aqueous solution was used.

[0369] Pure water is used as the pre-filling liquid. Nitrogen is bubbled into the pre-filling liquid at a nitrogen flow rate of 1 L / min. Note that water or aqueous solutions pre-placed in the reaction tank such as pure water here are sometimes referred to as pre-filling liquids. Pre-filling liquids are sometimes referred to as adjustment liquids. Pre-filling liquids and adjustment liquids refer to water or aqueous solutions before the reaction, i.e., water or aqueous solutions in the initial state.

[0370] The acid solution and the pre-filled solution were mixed at 0.10 mL / min and stirred at 1000 rpm. The pre-filled solution was maintained at pH 11.0 by dropping the alkaline solution appropriately. In addition, the temperature of the pre-filled solution was maintained at 50° C. In addition, a baffle was set in the reaction tank to change the stirring direction and flow rate. OptiMax (manufactured by Mettler-Toledo Co., Ltd.) was used in the above coprecipitation reaction.

[0371] The precipitate generated by the above coprecipitation reaction was filtered with pure water and acetone, and dried in a vacuum drying oven at 200° C. for 12 hours to obtain a composite hydroxide.

[0372] exist Figure 7 In step S41, lithium hydroxide is prepared as a lithium source. The lithium hydroxide is crushed by a fluidized bed airflow mill. In step S42, the composite hydroxide obtained above is mixed with a lithium source. When the sum of the atomic numbers of nickel, cobalt and manganese is 1, the mixing ratio of lithium is 0.7 (atomic number ratio).

[0373] In step S43, the mixture of the composite hydroxide and the lithium source is heated. The mixture is heated at 700°C for 10 hours using an alumina crucible in a muffle furnace under an oxygen atmosphere. The oxygen flow rate is 5 L / min and the temperature is increased by 100°C / hour. The mixture is then cooled to room temperature and ground (step S44), thereby obtaining a composite oxide (step S44).

[0374] In step S51, lithium hydroxide is prepared in the same manner as in step S41. In step S52, the composite oxide obtained above is mixed with a lithium source. When the sum of the atomic numbers of nickel, cobalt, and manganese is 1, the mixing ratio of lithium is 0.31 (atomic number ratio). That is, when the sum of the atomic numbers of nickel, cobalt, and manganese is 1, the total amount of lithium mixed in steps S42 and S52 is 1.01 (atomic number ratio).

[0375] In step S53, the mixture of the composite oxide and the lithium source is heated. The heating is performed in the same manner as in step S43 except that the heating temperature is 850°C. Then, the mixture is cooled to room temperature and ground (step S54), thereby obtaining a positive electrode active material. This positive electrode active material is recorded as sample 1.

[0376] A positive electrode active material produced in the same manner as Sample 1 in Step S53 except that the heating temperature was 875° C. is referred to as Sample 2.

[0377] A positive electrode active material produced in the same manner as Sample 1 in Step S53 except that the heating temperature was 900° C. is referred to as Sample 3.

[0378] In addition, as a comparative example, a positive electrode active material was manufactured with the mixing number of lithium sources being 1. Specifically, in step S41, when the sum of the number of atoms of nickel, cobalt, and manganese was 1, lithium was mixed in a manner of 1.01 (atomic number ratio), and no mixing was performed in step S52. The positive electrode active material manufactured in the same manner as sample 1 except for this was recorded as sample 4.

[0379] In addition, a positive electrode active material produced by heating Sample 4 at 800° C. for 10 hours is referred to as Sample 5.

[0380] <Sample 6 to Sample 9> As step S13, glycine weighed in an acid solution to 0.100 mol / L was prepared. A 0.100 M glycine aqueous solution was used as a pre-filling liquid. In addition, the acid solution was mixed into the pre-filling liquid at 0.0443 mL / min. In addition, after the coprecipitation reaction, the liquid temperature was controlled to 25° C., filtered with pure water, and then filtered with acetone.

[0381] In addition, Sample 6, Sample 7, Sample 8, and Sample 9 were respectively heated at 800°C for 10 hours after Step S54 (Step S55) and ground (Step S56). Except for the heating temperature, the same process as Step S43 was performed. The positive electrode active materials manufactured in the same manner as Samples 1 to 4 under other conditions were recorded as Samples 6 to 9.

[0382] <Sample 21> Furthermore, a positive electrode active material was produced in the same manner as Sample 8 except that heating was performed at 800° C. for 2 hours after the heating and cooling in step S55 . This material is referred to as Sample 21 .

[0383] Table 1 shows the manufacturing conditions of Samples 1 to 9 and Sample 21.

[0384] [Table 1]

[0385] <sem> Fig.21A , Fig. 21B , Fig. 21C , Fig.21D , Fig.21E and Fig.21F The SEM images of sample 1, sample 2, sample 3, sample 6, sample 7, and sample 8 are shown respectively. In these SEM images, positive electrode active materials with larger primary particles are confirmed. In addition, in samples 1 to 3 without S55 heating, it is observed that there are attachments on the surface of the positive electrode active material that can be inferred to be residues of lithium sources, etc. On the other hand, smooth surfaces with almost no residues are observed in samples 6 to 8 that are heated by S55.

[0386] <Grain size> The crystal grain size of each of Samples 1 to 9 was calculated by XRD analysis. The XRD apparatus and calculation method are the same as those described in Embodiment 1. Table 1 also shows the crystal grain size.

[0387] As shown in Table 1, the grain sizes of samples 1 to 3 and 6 to 8 manufactured by adding the lithium source in multiple steps are larger than those of samples 4, 5, and 9 manufactured by adding the lithium source all at once. The grain size of the sample manufactured by adding the lithium source all at once is less than 140 nm, while the grain size of the sample manufactured by adding the lithium source in multiple steps is 140 nm or more, more specifically, 150 nm or more.

[0388] <Half-cell charge and discharge rate characteristics> The charge and discharge rate characteristics were evaluated by assembling half cells using the positive electrode active materials of samples 7 to 9. By evaluating the cycle characteristics of the half cells, the performance of a single positive electrode was understood.

[0389] The conditions of the half-cell are described below. First, prepare the above-mentioned positive electrode active material, prepare acetylene black (AB) as a conductive material, prepare polyvinylidene fluoride (PVDF) as a binder, mix them in a manner of positive electrode active material: AB: PVDF = 95:3:2 (weight ratio) to make a slurry, and apply the slurry on the aluminum current collector. As a solvent for the slurry, use NMP.

[0390] After applying the slurry to the current collector, the solvent is evaporated. After the above steps, the positive electrode is obtained. The active material loading of the positive electrode is about 7 mg / cm 2 .

[0391] The electrolyte used was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a ratio of EC:DEC = 3:7 (volume ratio) with 2 wt% of vinylene carbonate (VC) added as an additive, and the electrolyte contained in the electrolyte used 1 mol / L of lithium hexafluorophosphate (LiPF6). Polypropylene was used as a separator.

[0392] Lithium metal is prepared as a counter electrode, and a coin-type half-cell including the above-mentioned positive electrode and the like is formed.

[0393] <Discharge rate characteristics> The discharge rate of the half-cell was measured.

[0394] Fig.22A The discharge capacities at 0.5C, 10C, and 20C measured at 25°C are shown. Fig. 22B The discharge capacities at 0.5C, 10C, and 20C measured at 65°C are shown. Charging was performed at CC / CV (constant current / constant voltage) (0.5C, 4.5V, 0.05C cut), and discharging was performed at CC (constant current) (0.5C, 10C or 20C, 2.5V cut). Note that 1C is set to 200mA / g.

[0395] like Fig.22A and Fig. 22B As shown, compared with the positive electrode active material with a smaller grain size such as sample 9, the secondary battery using the positive electrode active material with a larger grain size such as sample 7 and sample 8 exhibits a high discharge capacity at a high discharge rate exceeding 10C. For example, the discharge capacity at 25°C and 10C is 70mAh / g or more, and more specifically, the discharge capacity of sample 8 is 85mAh / g, and the discharge capacity of sample 7 is 98mAh / g. In addition, the discharge capacity at 65°C and 10C is 150mAh / g or more, and more specifically, the discharge capacity of sample 7 is 158mAh / g, and the discharge capacity of sample 8 is 168mAh / g. In addition, the discharge capacity at 65°C and 20C is 100mAh / g or more, and more specifically, the discharge capacity of sample 8 is 111mAh / g, and the discharge capacity of sample 7 is 124mAh / g.

[0396] <Charge rate characteristics> Next, a half-cell was manufactured using Sample 21 in the same manner as above, and its charge rate characteristics were evaluated.

[0397] Fig.23A The discharge capacities at 0.1C, 0.5C, 1C, and 5C measured at 25°C are shown. Fig. 23B The discharge capacity of 0.1C, 0.5C, 1C and 5C measured at 65°C is shown. Charging was performed at CC / CV (0.1C, 0.5C, 1C or 5C, 4.5V, 0.05C cut), and discharging was performed at CC (0.5C, 2.5V cut). The horizontal axis represents the rate during charging and discharging as C-rate. The charging rates of 0.1C, 0.5C, 1C and 5C were tested twice each.

[0398] like Fig.23A and Fig. 23B As shown in the figure, even if the charge rate changes from 0.1C to 0.5C, the discharge capacity does not change much, and sufficient charge and discharge can be performed at a high charge rate. For example, the discharge capacity at 25°C and 5 / 0.5 (charge / discharge) C is more than 150mAh / g, and more specifically, the discharge capacity at both times is 170mAh / g. In addition, the discharge capacity at 65°C and 5 / 0.5 is more than 170mAh / g, and more specifically, the discharge capacity at the first 5 / 0.5 is 180mAh / g and the second is 184mAh / g.

[0399] From the above results, it is understood that the positive electrode active material according to one embodiment of the present invention having a large crystallite size has excellent charge and discharge rate characteristics. [Example 2]

[0400] In this embodiment, the positive electrode active material 100 is manufactured, in which the crystal grain size of primary particles is large and the surface layer portion 100 a thereof includes an additive element.

[0401] <Manufacturing of Positive Electrode Active Material> Reference Figure 6 and Figure 8 The manufacturing method shown illustrates the samples manufactured in this embodiment.

[0402] First, the composite oxide is produced through steps S11 to S56 in the same manner as in Example 1 (step S57). Figure 8 In step S71, aluminum hydroxide is prepared as an aluminum source of the additive element. In step S72, the composite oxide is mixed with the aluminum source. When the sum of the atomic numbers of nickel, cobalt and manganese is 1, the mixing ratio of aluminum is 0.01 (atomic number ratio).

[0403] As step S73, the mixture of the composite oxide and the aluminum source is heated. The heating temperature is 800° C. and the heating time is 2 hours. The same steps as step S43 are performed except that the mixture is cooled to room temperature and ground (step S74), thereby obtaining a positive electrode active material. This is recorded as sample 32.

[0404] Magnesium was used as an added element, magnesium carbonate was prepared as a magnesium source, and the mixing ratio of magnesium was 0.01 (atomic number ratio) when the total number of atoms of nickel, cobalt and manganese was 1. Except for this, the positive electrode active material was manufactured in the same manner as sample 32, and this was recorded as sample 33.

[0405] A positive electrode active material was produced in the same manner as Samples 32 and 33 except that aluminum and magnesium were used as additive elements at a mixing ratio of 0.005 (atomic ratio) and 0.005 (atomic ratio). This is referred to as Sample 34.

[0406] A positive electrode active material was produced in the same manner as Sample 32 except that no additional element was added. This material is referred to as Sample 31.

[0407] Table 2 shows the manufacturing conditions of Samples 31 to 34.

[0408] [Table 2]

[0409] <Surface SEM> Fig.24A , Fig. 24B , Fig.24C and Fig.24D The surface SEM image of sample 31, the surface SEM image of sample 32, the surface SEM image of sample 33, and the surface SEM image of sample 34 are shown respectively. Fig.24E , Fig.24F , Figure 24G and Fig.24H Shown separately Fig.24A The enlarged image of the quadrilateral is attached. Fig. 24B The enlarged image of the quadrilateral is attached. Fig.24C The enlarged image of the quadrilateral is attached. Fig.24D An enlarged image of the quadrilateral portion is attached.

[0410] <Cross-sectional SEM-EDX> then, Fig.25A , Fig.25B and Fig.25C A cross-sectional SEM image of sample 32 , a cross-sectional SEM image of sample 33 , and a cross-sectional SEM image of sample 34 are shown. Fig.25D Show Fig.25A The aluminum concentration is measured by EDX point analysis of the portion shown in (1) to (4). Fig.25E Show Fig.25B The magnesium concentration in the parts shown in (1) to (4). Fig.25F Show Fig.25C The aluminum concentration and magnesium concentration of the portion shown by (1) to (4) in FIG. 1 are shown in FIG. 1. In each of the above figures, the aluminum concentration and the magnesium concentration decrease from the surface layer portion 100a toward the inside.

[0411] Depend on FIG. 24A to FIG. 25F It can be seen that the positive electrode active materials of samples 32 to 34 have a large crystal size and the concentration of the added element in the surface layer portion 100 a is higher than that in the interior. [Explanation of symbols]

[0412] 100: positive electrode active material, 100a: surface part, 100b: surface part, 100c: interior, 101: grain boundary, 104: coating< / sem> < / edx> < / xps> < / xrd>

Claims

1. A positive electrode active material comprising: Transition metal M, oxygen and added elements, Wherein, the transition metal M is nickel, manganese and cobalt, The added element is one or more selected from magnesium, aluminum, calcium, titanium and zirconium. The positive electrode active material includes a first surface layer, a second surface layer, and an interior. The second surface layer portion is closer to the interior than the first surface layer portion, The ratio of nickel in the interior to the total number of transition metal M atoms is higher than that in the first surface portion and the second surface portion. The ratio of the number of atoms of at least one element selected from cobalt and manganese in the second surface portion to the total number of atoms of the transition metal M is higher than that in the interior. Furthermore, the concentration of at least one of the additional elements in the first surface portion is higher than that in the interior and the second surface portion.

2. The positive electrode active material according to claim 1, The crystallite size of the positive electrode active material calculated from the XRD pattern is 150 nm or more.

3. A secondary battery comprising: A positive electrode and a negative electrode containing a positive active material, Wherein, the positive electrode active material includes transition metal M, oxygen and added elements, The transition metal M is nickel, manganese and cobalt, The added element is one or more selected from magnesium, aluminum, calcium, titanium and zirconium. The positive electrode active material includes a first surface layer, a second surface layer, and an interior. The second surface layer portion is closer to the interior than the first surface layer portion, The ratio of nickel in the interior to the total number of transition metal M atoms is higher than that in the first surface portion and the second surface portion. The ratio of the number of atoms of at least one element selected from cobalt and manganese in the second surface portion to the total number of atoms of the transition metal M is higher than that in the interior. Furthermore, the concentration of at least one of the additional elements in the first surface portion is higher than that in the interior and the second surface portion.

4. The secondary battery according to claim 3, The crystallite size of the positive electrode active material calculated from the XRD pattern is 150 nm or more.

5. A positive electrode active material comprising: transition metal M and oxygen, Wherein, the transition metal M is nickel, manganese and cobalt, The crystallite size of the positive electrode active material calculated from the XRD pattern is 150 nm or more. Furthermore, a secondary battery using the positive electrode active material has a discharge capacity of 70 mAh / g or more when subjected to CC / CV charging at 25° C. with a maximum voltage of 4.5 V, a constant current of 100 mA / g, and a cutoff current of 10 mA / g, followed by CC charging at 2000 mA / g.

6. A secondary battery comprising: A positive electrode and a negative electrode containing a positive active material, Wherein, the positive electrode active material includes transition metal M and oxygen, The transition metal M is nickel, manganese and cobalt, The crystallite size of the positive electrode active material calculated from the XRD pattern is 150 nm or more. The secondary battery has a discharge capacity of 70 mAh / g or more after CC / CV charging at 25° C. with a maximum voltage of 4.5 V, a constant current of 100 mA / g, and a cutoff current of 10 mA / g, followed by CC charging at 2000 mA / g.